Metabarcoding reveals soil fungal diversity shifts in the artificial cloud forest and volcanic desert of Ascension Island - Kleopatra Grammatiki; Nadieh de Jonge; Jacob Hargreaves; Michele Cleary; Diana Marčiulynienė; Eleni Kytinou; Akira F. Peters; Thomas Freitag; Pieter van West; Frithjof C. Küpper; Steve Woodward (Fungal Ecology, 2026)

Biogeochemical controls on water quality functions in resident Spartina and migratory mangrove wetlands following dredged sediment thin-layer placement - Nicholas Lonergan; Jacob F. Berkowitz; John R. White (Ecological Engineering, 2026)

Testing NetLogo model code - Steven F. Railsback; Jocelyn Bliven; Volker Grimm; Jacob Kelter (Ecological Modelling, 2026)

Understanding the importance of social and environmental stressors in predicting maternal sleep quality during late pregnancy - Xiaoran Yang; Sandrah P. Eckel; Yuhong Hu; Yan Xu; Roxana Khalili; Aviva Wolf-Jacobs; Tingyu Yang; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; Claudia M. Toledo-Corral; Jill Johnston; et al. (Environmental Research, 2026)

Multiphysics modeling of high-surface area carbon supports for polymer electrolyte fuel cells - Alper Can Ince; Mustafa Fazil Serincan; Siddharth Komini Babu; Jacob S. Spendelow; Edward F. Holby; Ugur Pasaogullari; Wilton J.M. Kort-Kamp (Chemical Engineering Journal, 2026)

Enhancement of photoelectrochemical water oxidation of surface-modified BiVO4/TiO2(001) via efficient cascade hole transfer - Munawar Khalil; Hafidatul Wahidah; Tribidasari A. Ivandini; Grandprix T.M. Kadja; Uji Pratomo; Muhammad N. Avicenna; Jacob Y. Mulyana; Fatwa F. Abdi; Andrivo Rusydi (Fuel, 2026)

Pasture-finishing enhances phytonutrients and fat-soluble vitamin profiles while grain-finishing enhances B-vitamins in beef from north American commercial operations - Muhammad Ahsin; Joseph Vinod Varre; Lamis Ali; Jennifer Cloward; Marina Carbonell Herrera; Camille Mittendorf; Travis Statham; Sree Bhavya Immadi; Ying Xi; Chyanne Crompton; Autumn F. Smith; Sagara Kumara; et al. (Food Chemistry, 2026)

Associations between perfluoroalkyl substances and multiple sclerosis in U.S. cohorts compared with NMOSD, MOGAD, and healthy controls - Farren B.S. Briggs; Federico Montini; Charles F. Spurlock; Christine Ryan; Jessica N. Cooke Bailey; Erika S. Trapl; Guzel I. Shaginurova; Lukasz S. Wylezinski; Cheryl L. Sesler; Mahboobeh Fereidan Esfahani; Jessica Sagen; Hannah E. Gardener; et al. (Environmental Research, 2026)

Cost-effectiveness and equivalence of methods to measure short-term sediment deposition and accretion rates - Jacob M. Berna; Nicole G. Dix; Scott F. Jones (Wetlands Ecology and Management, 2026)

Seasonal Shifts in Hydric Soil Morphology: Implications for Wetland Delineation - Sydney D. Bufkin; Jacob F. Berkowitz (Wetlands, 2026)
The identification and delineation of wetlands requires documentation of hydric soils, wetland hydrology, and hydrophytic vegetation. However, identifying hydric soils that exhibit high chroma colors remains challenging as they often lack diagnostic morphological features associated with established Field Indicators of Hydric Soils. In response, this study investigated problematic soil situations in the Slate Belt region of North Carolina using the Hydric Soil Technical Standard (HSTS). Ten study locations were monitored for water table level, anaerobic conditions, and soil morphology over time. Results show dynamic shifts in soil morphological characteristics, with seven locations meeting HSTS requirements and all locations meeting one of more Field Indicator of Hydric Soils during the wet portion of the growing season. However, by July, no study locations met the HSTS criteria, and only three locations continued to exhibit a Field Indicator of Hydric Soils. The study highlights the importance of considering seasonal variations and dynamic soil processes in problematic high chroma soils during hydric soils identification and wetland delineation. When evaluating these soils, practitioners should conduct field assessments during the normal wet portion of the growing season to obtain accurate assessments of wetland resources. This study’s findings have implications for wetland management and call for further research to understand seasonal shifts in high chroma soil morphology, especially in rapidly urbanizing regions.

Columnanidus calitzdorpensis ichnogen. ichnosp. nov: A new Middle Pleistocene subterranean termite trace fossil from South Africa - Miengah Abrahams; Robert A. Muir; Jorge F. Genise; John E. Almond; Gcinamahlubi Hadebe; John C. Hellstrom; Rabia Jacobs; Chris Harris (Journal of Quaternary Science, 2026)
Termites are landscape geo‐engineers whose nesting activities substantially modify the physical and chemical properties of soils. Fossilised termite nests commonly constitute the only identifiable evidence of ancient termite activity and represent valuable trace fossil archives for reconstructing past environments. Here, we describe a new ichnogenus and ichnospecies, Columnanidus calitzdorpensis ichnogen. ichnosp. nov., from Quaternary alluvial deposits near Calitzdorp, South Africa. The subterranean nests are subcylindrical structures, reaching ~1 m in height and ~65 cm in diameter, and are characterised by a ~12 cm wide, shelved nest wall surrounding an empty central cavity. Within the nest wall, the gallery and chamber morphology and abundance vary between the inner and outer zones. The nests are preserved as calcretised features, composed of inter‐laminations of clastic sediment and pedogenic carbonate precipitate. U‐series dating of the carbonate laminations yields robust age peaks at 401 ± 46 ka and 323 ± 12 ka, indicating a Middle Pleistocene minimum age for nest formation. These ages coincide with intervals favourable for pedogenic carbonate development under semi‐arid to arid climatic conditions. Hardpan calcretes capping the nests suggest prolonged periods of semi‐arid conditions and sustained pedogenic stability during the Middle Pleistocene in the Calitzdorp region.

Habitat suitability ensembles of genotype and disease resistance for Juglans cinerea to assist restoration efforts - Carlisle S. Bascom; Anna O. Conrad; Aziz Ebrahimi; Douglass F. Jacobs; Carrie Fearer (Forest Ecology and Management, 2026)

Range-wide monitoring reveals demographic vulnerability in Lahille's bottlenose dolphins - Fábio G. Daura-Jorge; Paula Laporta; Ignacio B. Moreno; Paulo H. Ott; Paulo A.C. Flores; Pedro Volkmer de Castilho; André S. Barreto; Rodrigo Cezar Genoves; Carolina Bezamat; Alexandre M.S. Machado; Eduardo R. Secchi; Silvina Botta; et al. (Biological Conservation, 2026)

Design and validation of an SNP-based assay for detecting Juglans ailantifolia introgression into Juglans cinerea populations or living collections - Martin Williams; Manuel Lamothe; Aziz Ebrahimi; Berni M. van der Meer; Mojtaba Zamani Faradonbeh; Anna O. Conrad; James Warren; Carolyn C. Pike; Douglass F. Jacobs; Nathalie Isabel (Tree Genetics & Genomes, 2026)
Butternut ( Juglans cinerea L.) is a rapidly declining tree species threatened by Ophiognomonia clavigignenti-juglandacearum (Oc-j), the causal agent of butternut canker. The introduction of Japanese walnut ( Juglans ailantifolia Carrière), which hybridizes with butternut and exhibits greater resistance to the disease, presents both a conservation challenge and a potential avenue for genetic improvement. Identifying non-admixed butternuts is critical for conservation efforts and breeding programs aimed at preserving the species’ genetic integrity while exploring resistance strategies. However, morphological identification of first and advanced generation hybrids is unreliable, necessitating the development of efficient detection tools. In this study, we developed and validated a cost-effective, high-throughput SNP genotyping tool using the MassARRAY platform to distinguish between J. cinerea , J. ailantifolia , and their hybrids. The panel consists of 28 nuclear SNPs and two chloroplast SNPs and demonstrates strong concordance with genotyping-by-sequencing (GBS) results using nearly 12,000 SNPs (R² = 0.98), indicating high predictive accuracy. Field testing this genotyping tool to 1,269 trees from natural stands and breeding programs in Canada and the U.S. revealed substantial hybridization, particularly in U.S. plantations, where hybrids comprised up to 18% of tested trees. Chloroplast analysis confirmed asymmetrical hybridization patterns, with J. ailantifolia acting predominantly as the maternal parent. This SNP panel provides a valuable tool for conservation, breeding, and regulatory applications by enabling rapid and accurate hybrid identification. Its implementation will help guide recovery strategies for butternut, ensuring that conservation efforts are informed by precise genetic data.

Wetlands and warfare — implications for hydrologic and biogeochemical ecosystem functions - Yadav Sapkota; Marissa L. Kneer; Evan S. Grimes; Jacob F. Berkowitz (Environmental Management, 2026)

Joint optimization of a GRACE radiation pressure model, the accelerometer scale factors, and an empirical magnetic-field-induced accelerometer bias - F. Jacobs; N. Hładczuk; J. van den IJssel; C. Siemes; P. Visser (Advances in Space Research, 2026)

Temperature Predicts Relative Mass but Not Size in Passerines - Charlotte M. Probst; Jacob S. Berv; Zhizhuo Zhou; Mingyu Zhang; Tiffany Dias; Karen Alofs; David F. Fouhey; Brian C. Weeks (Global Ecology and Biogeography, 2026)
Aim Predictable relationships between temperature and animal size and shape are the basis for classic rules in macroecology. Body size is thought to covary negatively with temperature (Bergmann's Rule), broadly attributed to thermoregulatory demand for larger size in colder climates. However, ecophysiological principles suggest that changes in insulative materials may be a more effective thermoregulatory adaptation than changes in overall skeletal size. We test for global gradients in mass relative to skeletal size (a proxy for insulation) and body size. Location Global. Time Period Current. Major Taxa Studied Aves: Passeriformes. Methods Combining a dataset of mass and skeletal traits for 1958 passerine species, we use Bayesian phylogenetic comparative analyses to test the extent to which temperature predicts skeletal size and relative mass. Results Across species, we find no evidence that temperature predicts skeletal size; rather, the effects associated with phylogeny account for nearly all of the variation in size. In contrast, we find a global gradient in mass relative to skeletal size, with species in colder climates having more mass than expected given their skeletal size. For 24 species, we assess these relationships within species and find that relative mass has declined through time but is not predicted by temperature. Main Conclusions Mass relative to skeletal size is expected to exert a significant effect on insulation and energy stores, and we find it is more labile than skeletal size across species. Our results suggest: (1) species in colder climates tend to have greater insulation (as indicated by their higher relative mass); (2) skeletal size in passerines does not strongly adhere to Bergmann's Rule, suggesting spatial temperature‐size relationships may be unlikely to predict temporal responses of size to climate change in this group; and (3) declines in relative mass may be a widespread cryptic response to global change.

Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Determining the roots of Urnfield Culture at Přáslavice, Czech Republic - Christina Cheung; Klára Šabatová; Ivana Jarošová; Kévin Salesse; Hannah F. James; Jacob I. Griffith; Zdeněk Tvrdý; Christophe Snoeck (Archaeological and Anthropological Sciences, 2026)
This study examines the residential mobility patterns and funerary practices of an Urnfield cemetery at Přáslavice, Czech Republic, using radiocarbon dating, carbon, oxygen, and strontium isotope analyses, and FTIR analysis. A regional bioavailable strontium baseline map was created using strontium isotope ratios ( 87 Sr/ 86 Sr) of modern plant samples (n=208) from 70 localities across Moravia and Czech Silesia. Radiocarbon dates (n=17) suggest that the cemetery was primarily in use during the Late Bronze Age (1300–1100 BCE), with some burials dated to the Final Bronze Age (1100–800 BCE). Most of the Late Bronze Age burials have homogenous 87 Sr/ 86 Sr values (0.7114–0.7128) well within the established local Sr baseline, thus supporting the hypothesis that Urnfield at Přáslavice was a local development. FTIR and carbon and oxygen isotope analyses also suggest the group practiced cremation similarly to other Urnfield populations. Overall, this study not only enhances our knowledge of the social dynamics and funerary practices at Přáslavice, but also establishes a crucial bioavailable Sr baseline for future palaeomobility studies in the region.

Optimal Environmental Window of the Recruitment of Thread Herring Opisthonema libertate in the Southern Gulf of California - Efrain Delgado‐Robles; Mercedes L. Jacob‐Cervantes; Emigdio Marín‐Enríquez; Jorge Payán‐Alejo; Luis A. Salcido‐Guevara; J. Roberto F. Vallarta‐Zárate (Fisheries Oceanography, 2026)
The recruitment processes in small pelagic populations are an important topic for assessment and management. Different hypotheses have been proposed to explain how some environmental variables like upwelling and turbulence affect it. The main hypothesis is the optimal environmental window (OEW) hypothesis: 5–6‐m/s wind speed as an OEW. However, this generalization may not apply to all species. In this study, we proposed that OEW should be determined according to an optimal recruitment level. For this, data for Ekman transport components and wind speed were used to calculate the upwelling (UI) and turbulence (TI) indices in the southern Gulf of California (SGC). Recruits (Rec) and spawners (SP) annual data of Opisthonema libertate were obtained from the 2021 official stock assessment. A stepwise procedure was used to fit a generalized additive model (GAM) to Rec data with UI, TI, and SP as covariates. Based on an 11‐step algorithm, we determined the OEW of recruitment for this species using partial effects analysis from GAMs. The relationships between the predictors and Rec were nonlinear (dome‐shaped). The OEW of recruitment for this species using the proposed approach was 5.29–22.72 m 3 /s per 100 m of coastline for UI and 79.56–106.67 m 3 /s 3 for TI. These results showed that O. libertate recruitment in the SGC is maximized under moderate upwelling and turbulence conditions, and that the proposed approach to determine the OEW is functional when the relationship between predictor variables and recruitment is nonlinear.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Heme Iron Polypeptide Resolves Iron-deficiency Anemia in Rats and Mice - Yue He; Jacob S. Shine; Sitara Sriram; Melissa Fraga; Li-Ying Kuo; Jennifer K. Lee; Xiaojing Yuan; Iqbal Hamza; James F. Collins (Biological Trace Element Research, 2026)

Molecular approaches to increasing plant root carbon - Declan Lafferty; Jacob Calabria; Ryan Lister; Jorge E. Mayer; Michelle Watt; John F. Golz (Trends in Plant Science, 2026)

Nonlinear relationships between deer harvests, agriculture, and deer-vehicle collisions - Mark E. Bell; David S. Mason; Kenneth F. Kellner; Jacob E. Hill; Chad Stewart; Jerrold L. Belant (Environmental Impact Assessment Review, 2026)

Genomic Signatures of Microgeographic Adaptation in Anopheles coluzzii Across Urban, Rural, and Forested Environments in Gabon - Josquin Daron; Lemonde Bouafou; Jacob A. Tennessen; Nil Rahola; Loic Talignani; Boris Makanga; Ousman Akone‐Ella; Marc F. Ngangue; Neil M. Longo Pendy; Christophe Paupy; Daniel E. Neafsey; Michael C. Fontaine; et al. (Molecular Ecology, 2026)
Species distributed across heterogeneous environments often evolve locally adapted populations, but understanding how these persist in the presence of homogenizing gene flow remains puzzling. In Gabon, Anopheles coluzzii, a major African malaria mosquito, is found in various ecological settings, including urban areas, remote rural villages, and forested environments away from any human presence. This study investigates the genomic signatures of local adaptation in populations from distinct environments including the urban area of Libreville, and two proximate sites 10 km apart in the La Lopé National Park (LLP), a village and its sylvatic neighbourhood. Whole genome re‐sequencing of 96 mosquitoes unveiled 5.9 million high‐quality single nucleotide polymorphisms. Coalescent‐based demographic analyses suggest an ∼ 12,000‐year‐old divergence between Libreville and La Lopé populations, followed by a secondary contact ( ∼ 4000 ybp) resulting in asymmetric effective gene flow. The urban population displayed reduced effective size, evidence of inbreeding, and strong selection pressures likely associated to insecticides or pollution present in urban settings, as suggested by the hard selective sweeps detected in genes involved in detoxification and insecticide resistance. In contrast, the two geographically proximate LLP populations showed larger effective sizes, and distinctive selective signals, notably soft‐selective sweeps on the standing genetic variation. Although presumably neutral loci failed to discriminate between LLP populations, our findings support that microgeographic adaptation can swiftly emerge through selection on standing genetic variation despite gene flow. This study contributes to the growing understanding of evolution of populations in heterogeneous environments amid ongoing gene flow and how major malaria mosquitoes adapt to humans and its environment.

Identification of Genetic Variation Associated With Heat Tolerance in Cowpea ( Vigna unguiculata L. Walp.) - Roland Akakpo; Elaine J. Lee; Jacob B. Pacheco; Esteban F. Rios; Michael B. Kantar; Ousmane Boukar; Kevin M. Volz; Habib Akinmade; Luis Getino; Kenneth J. Boote; María Muñoz‐Amatriaín; Peter L. Morrell (Molecular Ecology, 2026)
Heat tolerance is an important trait in cowpea, a crop that is the primary protein source for a large portion of the human population in sub‐Saharan Africa. Cultivated, landrace, semi‐wild, and wild cowpea grow across the region in diverse climatic conditions. This study used environmental association (envGWAS) and allele‐frequency outlier approaches across a panel of 580 gene bank accessions to identify genomic regions associated with adaptation to heat and limited precipitation. Allele frequency outliers are detected independent of potential selective factors driving differentiation; we used a ranking‐based approach to identify the climate variables most associated with variants among outliers. Precipitation‐related variables dominated the signals we identified for envGWAS and allele frequency outliers. We identified variants on all 11 chromosomes that are putatively associated with cowpea adaptation to higher‐temperature environments. The overlap between variants associated with low precipitation and high temperature suggests that these traits may be inextricably linked in cowpea. The Sahel region is the source of many accessions with derived variants associated with high temperatures, suggesting that accessions from this region could contribute heat tolerance alleles for cowpea improvement.

Ink to innovation: Pioneering printing technologies for next-generation drug delivery systems - Noha F. Ghazi; Vincenzo Taresco; Philippa L. Jacob; Thatayaone Monkgogi; Jonathan C. Burley; George Bebawy (Drug Delivery and Translational Research, 2026)

Species diversity and competition influence nitrogen resorption efficiency in mixed hardwood plantations - Taylor M. Nelson; Minjee Park; Lorenzo Cotrozzi; Kliffi M. S. Blackstone; Gordon G. McNickle; Douglass F. Jacobs; John J. Couture (Oecologia, 2026)
Nutrient dynamics substantially influences forest productivity, yet the influence of competition on these processes in forests is not well understood. Nitrogen is an important limiting nutrient for tree growth, but how canopy nitrogen dynamics are influenced by tree diversity and competition is unclear. Nitrogen-use efficiency is one mechanism suggested to support niche complementarity, promoting increased productivity as diversity increases, and is influenced by the resorption of foliar nutrients during senescence. We tested how diversity and competition affect canopy nitrogen dynamics by examining nitrogen resorption efficiency (NRE) in over 200 trees from three tree species in a 12-year-old mixed-species hardwood planting that included a full-factorial design of three levels of species diversity, representing intra- and interspecific competition, and two levels of planting density, representing competition intensity. Midseason and senescent foliar samples were collected from black cherry ( Prunus serotina ), American chestnut ( Castanea dentata ), and northern red oak ( Quercus rubra ) and we determined midseason canopy and foliar litter nitrogen concentrations and calculated NRE. Higher midseason canopy nitrogen concentrations were observed in more diverse, low-density plantings, but the response magnitude varied among species. NRE increased as diversity increased; the response, however, varied among species, ranging from a statistically significant increase to no response, but was not influenced by planting density. These findings provide evidence that while the influence of diversity on tree physiological responses depends on the type of competitive interaction (i.e., diversity or intensity), different combinations of species will likely affect processes related with niche complementarity and, ultimately, a positive biodiversity–productivity relationship.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Associations of forest vs. urban environmental exposure with well-being and nasal microbiome composition: An exploratory pilot study - D. Connor Lashus; Andres Gomez; Thomas Hummel; Lucia F. Jacobs; Asifa Majid; Ravikiran M. Raju; Caroline J. Smith; Jonathan Williams; Gregory N. Bratman (Environmental Research, 2026)

Prenatal exposure to heat stress and postpartum depressive symptoms in the MADRES cohort in urban Los Angeles - Yuhong Hu; Noelle Pardo; Xiaoran Yang; Tingyu Yang; Yan Xu; Roxana Khalili; Aviva Wolf-Jacobs; Xinci Chen; Zhongzheng Niu; Claudia M. Toledo-Corral; Jill Johnston; Genevieve F. Dunton; et al. (Environmental Research, 2026)

Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Holarctic species in the Pluteus ephebeus clade: description of four new species and revision of historical names - Hana Ševčíková; Ekaterina F. Malysheva; Vladimír Antonín; Francesco Dovana; Giuliano Ferisin; Django Grootmyers; Jacob Heilmann-Clausen; Guillermo Muñoz González; Andrew M. Minnis; Stephen D. Russell; Carmel Sammut; Michal Sochor; et al. (Systematics and Biodiversity, 2026)

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Cork oak seedling emergence, survival, and growth in response to active limestone and water stress conditions - Taher Mechergui; Marta Pardos; Douglass F. Jacobs; Arnab Banerjee; Filipe Xavier Catry (European Journal of Forest Research, 2025)

Upscaling nature-based solutions for reducing risk from natural hazards: From process to practice - Amanda Tritinger; Sydney Crisanti; Steven P. Bailey; Jacob F. Berkowitz; Elizabeth S. Godsey; Burton C. Suedel; Jeffrey K. King (Advances in Water Resources, 2025)

Solar and thermal radiation pressure modelling for improving the GOCE horizontal wind dataset - N.A. Hładczuk; J. van den IJssel; F. Jacobs; C. Siemes; P. Visser (Advances in Space Research, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Ni-Co-O anodes for the alkaline oxygen evolution reaction: Multistage electrode optimization and plasma-assisted activity enhancement enabled by a coherent workflow - Vineetha Vinayakumar; Timo Wagner; Christian Marcks; Jacob Johny; Garlef Wartner; Ahyoun Lim; Marc F. Tesch; Ioannis Spanos; Aliakbar Ghafari; Adarsh Jain; Oleg Prymak; Ignacio Sanjuán; et al. (Chemical Engineering Journal, 2025)

Revealing the unseen: 3D synchrotron X-Ray imaging of uterine vasculature in adenomyosis - Veerle M. W. Michels; Adam Szmul; Joseph Jacob; Hector Dejea; Bernadette S. de Bakker; Judith A. F. Huirne; Yousif Dawood; Daniël Docter; Lynda J. M. Juffermans; Nicole B. Burger; Richard A. Schoonhoven; Jermo Hanemaaijer - van der Veer; et al. (Angiogenesis, 2025)

Tropics to the Poles: A Snapshot of Coastal Eukaryotic Marine Microalgal Diversity Across Five Ecoregions - Jacqui Stuart; Ken G. Ryan; John K. Pearman; Natalie Robinson; Svenja Halfter; Jacob Thomson‐Laing; Laura Biessy; Kirsty F. Smith (Molecular Ecology, 2025)
Eukaryotic microalgae are key organisms in marine environments, contributing to essential nutrient and biogeochemical cycles. Climate change is already causing shifts in the composition and diversity of microalgal assemblages, with coastal ecosystems experiencing increased pressure. Molecular techniques, such as environmental DNA (eDNA) metabarcoding, have allowed eukaryotic microalgal communities (EMCs) to be characterised more rapidly than traditional methods, addressing some data gaps. Many geographic regions still lack comprehensive baseline assessments of entire EMCs, often focusing on specific taxonomic or functional groups. In this study, we used eDNA metabarcoding of the 18S V9 gene region to characterise EMCs across a latitudinal gradient spanning five ecoregions from the South Pacific to the Ross Sea. Temperate sites had the highest alpha diversity and the most distinct EMCs across all ecoregions. Community composition showed clear latitudinal gradients, with a shift from dinoflagellate‐dominant EMCs at lower latitudes to diatom‐dominant EMCs at higher latitudes. The formation of EMCs was influenced by similar habitats/conditions (homogeneous selection) and proximity (homogenising dispersal) within ecoregions, while variable conditions (variable selection) and limited interconnectivity (dispersal limitation) were more prevalent between ecoregions. This snapshot of coastal EMC diversity across five ecoregions highlights distinct latitudinal patterns in community composition, with temperate regions showing higher diversity compared to polar areas. These findings provide a useful baseline for future monitoring and can help guide assessments of potential changes in microalgal communities due to climate change.

Entangled ecosystems: the impact of macroplastic litter on Mytilus galloprovincialis communities in northwestern Spain - Jacob Houvener; Ignacio Moreu; Eva Cacabelos; Ignacio Gestoso; Jose M. F. Babarro; Mark Lenz (Frontiers in Marine Science, 2025)
Plastic litter in the ocean has gained significant attention over recent decades, with much of the focus on microplastics. However, macroplastic litter is prevalent in marine environments, and while its effects on single organisms is well documented, its effects on community-level biological structures remain poorly understood. This study investigates the impact of macroplastic litter—specifically polyethylene film (shopping bags) and nylon filament (fishing line)—on Mytilus galloprovincialis aggregates and their associated fauna in the Ría de Vigo, NW Spain. Using a fully factorial experimental design, 30-mussel aggregates were assembled incorporating plastic litter in different abundances and were deployed in situ for 4 weeks. After this time, physiological responses (respiration and filtration), structural complexity (rugosity index), particulate matter retention, body condition index (BCI), and associated mobile faunal diversity were measured. Mussels in the High/Filament treatment showed an 18% lower respiration rate and a 65% reduction in filtration capacity compared to controls, while the Low/Filament treatment reduced filtration by 40%. No significant effects were found on BCI, particulate retention as well as on the diversity and composition of the associated macrofauna. Interestingly, aggregates with low plastic content exhibited a slightly higher structural complexity than those with high amounts of plastic. This study highlights that macroplastics can subtly alter the functionality of mussel beds without dramatically affecting the diversity of the associated fauna. These insights underscore the need to assess physical interactions of organisms with plastic litter also at the community level.

Cultivation of Chlorella sp. in photobioreactors: Potential for bioremediation of synthetic soy milk effluents and biofuel production - Jacob Santana; Cecília de Mello; Mônica Silva dos Santos; Renata Vilas Boas; Leonardo Lucchetti; Marisa F. Mendes; Henrique Vieira de Mendonça (Journal of Environmental Chemical Engineering, 2025)

Application of mercury stable isotopes to examine sources and hydrologic factors impacting mercury bioaccumulation and cycling in invertebrates of a model saline lake - Samuel F. Lopez; Sarah E. Janssen; Michael T. Tate; Frank J. Black; Hannah E. McIlwain; Laura E. Flucke; Jacob M Ogorek; William P. Johnson (Water Research, 2025)

Leveraging technology and standardized institutional practices to mitigate disparities in breast cancer radiation therapy - Jacob F. Oyeniyi; Bailey A. Loving; Muayad F. Almahariq; Maha Saada Jawad; Joshua T. Dilworth (Cancer Causes & Control, 2025)

A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Nutrient Enrichment Increases Blue Carbon Potential of Subtropical Seagrass Beds - Bridget F. Shayka; Sean Richards; Mona A. Andskog; Jacob E. Allgeier (Global Change Biology, 2025)
Seagrass beds have potential as nature‐based solutions to climate change because their high rates of primary production can bury large amounts of carbon. Yet, realizing their potential necessitates improved understanding of the mechanisms contributing to carbon burial, especially in the context of nutrient enrichment, a ubiquitous threat to seagrass beds globally. Leveraging a nine‐year nutrient enrichment experiment, we tested how different nutrient sources, supply rates, and ratios altered mechanisms underpinning carbon burial. Nutrient enrichment increased aboveground and decreased belowground biomass but increased carbon production and turnover, particularly belowground. To inform conservation efforts, we showed that blade height and shoot density effectively predict belowground carbon turnover and therefore provide a simple measure to assess potential belowground carbon inputs to sediment. By identifying the mechanisms that promote carbon burial in the face of nutrient enrichment, our study advances understanding of how to prioritize protection of nature‐based solutions amidst this ubiquitous stressor.

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Comparing inward and outward strategies for delimiting non-native plant pest outbreaks - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Wopke van der Werf (Journal of Pest Science, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Transdisciplinary Collaborations for Advancing Sustainable and Resilient Agricultural Systems - Vesna Bacheva; Imani Madison; Mathew Baldwin; Justin Baker; Mark Beilstein; Douglas F. Call; Jessica A. Deaver; Kirill Efimenko; Jan Genzer; Khara Grieger; April Z. Gu; Mehmet Mert Ilman; et al. (Global Change Biology, 2025)
Feeding the growing human population sustainably amidst climate change is one of the most important challenges in the 21st century. Current practices often lead to the overuse of agronomic inputs, such as synthetic fertilizers and water, resulting in environmental contamination and diminishing returns on crop productivity. The complexity of agricultural systems, involving plant‐environment interactions and human management, presents significant scientific and technical challenges for developing sustainable practices. Addressing these challenges necessitates transdisciplinary research, involving intense collaboration among fields such as plant science, engineering, computer science, and social sciences. Five case studies are presented here demonstrating successful transdisciplinary approaches toward more sustainable water and fertilizer use. These case studies span multiple scales. By leveraging whole‐plant signaling, reporter plants can transform our understanding of plant communication and enable efficient application of water and fertilizers. The use of new fertilizer technologies could increase the availability of phosphorus in the soil. To accelerate advancements in breeding new cultivars, robotic technologies for high‐throughput plant screening in different environments at a population scale are discussed. At the ecosystem scale, phosphorus recovery from aquatic systems and methods to minimize phosphorus leaching are described. Finally, as agricultural outputs affect all people, integration of stakeholder perspectives and needs into research is outlined. These case studies highlight how transdisciplinary research and cross‐training among biologists, engineers, and social scientists bring diverse expertise to tackling grand challenges in sustainable agriculture, driving discovery and innovation.

Safety and immunogenicity of a sarcoid vaccine in horses - O. Jacob; B. Hause; K. Peters-Smith; E.N. Adam; A.E. Page; C. Floyd; C. Tucker; L.G. Eertink; D. Wang; F. Li (Journal of Equine Veterinary Science, 2025)

Correction: Outcomes of retesting in patients with previously uninformative cancer genetics evaluations - Shenin A. Sanoba; Erika S. Koeppe; Michelle F. Jacobs; Elena M. Stoffel (Familial Cancer, 2025)

Influence of ozonized autohemotherapy at acupuncture points on stallion sperm quality - J.C. Ferraz Jacob; P. Junqueira Ferraz; L. Bastos Mello Rosa; H. Siqueira da Costa e Souza; M. Tainá Resende Ribeiro; A.C. Oliveira de Andrade; V. Souza de Freitas; F. Batalha Knackfuss; V.L. Teixeira de Jesus; J.G. Fernandes Joaquim (Journal of Equine Veterinary Science, 2025)

Therapeutic potential of 2S-hesperidin against the hepatotoxic effects of dichlorvos in rats - Adio J. Akamo; Adetutu O. Ojelabi; Naomi M. Akamo; Ibiyemi O. Opowoye; Boluwatife A. Olagunju; Oluwatobi T. Somade; Ofem E. Eteng; Adedayo A. Adebisi; Taiwo S. Oguntona; Mushafau A. Akinsanya; Abiola F. Adenowo; Tolani E. Oladele; et al. (Food and Chemical Toxicology, 2025)

Functional habitat characteristics influencing spatial variation in mountain lion predation in a human-dominated landscape - Jacob A. Harvey; Quinton Martins; Kyle D. Dougherty; Alexandra M. Hettena; David K. Garcelon; John F. Benson (Biological Conservation, 2025)

Dynamics of rain-triggered lahars and destructive power inferred from seismo-acoustic arrays and time-lapse camera correlation at Volcán de Fuego, Guatemala - Ashley R. Bosa; Gustavo Bejar; Gregory P. Waite; Jerry C. Mock; Armando Pineda; Jacob F. Anderson (Natural Hazards, 2025)
Lahars, or volcanic mudflows, are one of the most devastating natural, volcanic hazards. Deadly lahars, such as the one that occurred after the Nevado del Ruiz, Columbia eruption in 1985, in which at least 23,000 people tragically lost their lives, threaten the safety and well-being of humans, the economy, and the infrastructure of many of the communities living in the vicinity of volcanoes. Due to their complex flow behaviors, lahars remain a major challenge to those studying them. We present an analysis of several rain-triggered lahar events at Volcán Fuego in Guatemala using both seismic and infrasound monitoring to quantify both ground vibrations and low-frequency atmospheric sound waves associated with these mudflows. Geophysical data collected over this field campaign quantifies flow parameters such as velocities, stage and the frequency of these rain-triggered lahars. Time-lapse imagery of lahar flows is compared with filtered seismo-acoustic signal characteristics to ascertain stage predictions and relationship to stage fluxes. Using random forest regression models, we establish moderate correlations (correlation coefficient modes 0.48–0.53) with statistical significance ( p value = 0.01–0.02) between signal energetics and respective stage. Compiling a catalog of rain-triggered lahar events in Volcán de Fuego’s drainages over a season permits a dataset amenable to statistical analysis. Our goal is the development of new-generation geophysical monitoring tools that will be capable of remote and real-time estimation of flow parameters.

Impacts of habitat loss by reservoir inundation on occurrence, abundance, and genetic diversity of an imperiled, river-adapted, benthic-specialist fish, Etheostoma lemniscatum (Tuxedo Darter) - Rebecca E. Blanton; Jacob F. Brumley; Matthew R. Thomas; Jeffrey W. Simmons; Stephanie L. Brandt; Michael A. Floyd (Conservation Genetics, 2025)
Dams homogenize habitat and alter natural depth and flow regimes of lotic habitats, leading to extirpation of many stream-adapted fishes such as darters (Percidae). The Tuxedo Darter, Etheostoma lemniscatum , is a habitat-specialist of shallow, flowing pools with cobble substrate in the Big South Fork Cumberland River. One threat to this species is Wolf Creek Dam on the Cumberland River that creates Lake Cumberland, which during summer pool, inundates the lower 72 river kilometers (rkms) of the Big South Fork. A six-year period of lower reservoir elevations for dam repairs allowed a 9 rkm reach to return to riverine habitat and E. lemniscatum to colonize this reach. Once dam repairs were complete, the lower 72 rkms were again regularly inundated by Lake Cumberland. To determine the impact of post-dam repair inundation on E. lemniscatum , we compared occurrence, abundance, and genetic diversity metrics estimated from samples from 2015 and from several years post-inundation in 2019 and 2020 from 11 sites spanning the species’ range. Declines in occurrence and abundance were detected within the re-inundated reach. We observed low genetic diversity for the species for both sample periods, but no significant changes in genetic diversity between years. A trend towards lower allelic richness and an increase in the proportion of private alleles was observed in the 2019/2020 samples. Coupled with local extirpation and declines in abundance, these trends may be early warning signs of future declines in genetic diversity. We suggest future genetic monitoring to identify any time delayed responses to inundation not detected herein.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Nuclear phylogenomics of Eperua (Leguminosae) highlights the role of habitat and morphological lability in dispersal and diversification across Amazonia and in the Caatinga-Cerrado ecotone - Elenice A. Fortes; Jacob B. Landis; Hans ter Steege; Chelsea D. Specht; Jeff J. Doyle; Vidal de F. Mansano (Molecular Phylogenetics and Evolution, 2025)

Focal pharmacological manipulation of serotonin signaling in the amygdala does not alter social behavior - Jessica T. Jacobs; Rafael S. Maior; Hannah F. Waguespack; Carolina Campos-Rodriguez; Ludise Malkova; Patrick A. Forcelli (Psychopharmacology, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Host associations of Campylobacter jejuni and Campylobacter coli isolates carrying the L-fucose or d-glucose utilization cluster - Pjotr S. Middendorf; Aldert L. Zomer; Indra L. Bergval; Wilma F. Jacobs-Reitsma; Heidy M.W. den Besten; Tjakko Abee (International Journal of Food Microbiology, 2024)

Food macroalgae: scoping review of aspects related to research and consumption - Lara Juliane Guedes da Silva; Alice Medeiros Souza; Priscila F. M. Lopes; Michelle Cristine Medeiros Jacob (Journal of Applied Phycology, 2024)

An investigation of personality in the Creek Chub, Semotilus atromaculatus - Jacob P. Barrett; Mollie F. Cashner (Environmental Biology of Fishes, 2024)
Intraspecific variation in personality traits is increasingly recognized as an important driver of ecological processes, particularly within the context of species invasions. However, relatively few studies have investigated personality in native fauna with more localized dispersal patterns, and information regarding the existence of personality in stream fishes native to the southeastern US is particularly lacking. In this study, we investigated personality in a native and widespread minnow species, the Creek Chub ( Semotilus atromaculatus ). Because of its piscivorous diet, use of its nests by nest-associating minnows, and its role as a colonizer of intermittent streams, the Creek Chub is an appropriate species for investigating the broad importance of personality-dependent processes to stream communities. We identified personality traits by estimating the repeatability of sociability, boldness, exploration, and activity in two separate behavioral assays and interpreted correlations between traits as evidence of behavioral syndromes. We did not detect repeatability for measures of sociability, possibly due to predatory interactions within this species. However, boldness, exploration, and activity were significantly repeatable and positively correlated, pointing to the existence of a bold-exploratory-active syndrome in this species. Larger individuals tended to be less active, and, despite a relatively small sample size, we detected significant differences between source populations for measures of boldness. This is the first study to identify the existence of a behavioral syndrome in Creek Chub and points to the importance of considering the role of personality in ecological processes involving native fauna.

Response of understory vegetation to long-term occupancy by introduced Pinus species in temperate deciduous hardwood forests - Patrick J. Duffy; Douglass F. Jacobs; John M. Kabrick; Christopher D. Thornton; J. Travis Swaim; Michael A. Jenkins (Forest Ecology and Management, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Development of a new accurate lateral flow immunoassay for diagnosis of human leptospirosis - Nazarena Pujato; Juan M. Gimenez; Leandro E. Peretti; Noelia Y. Landolt; Paulina Jacob; Yosena T. Chiani; Maria F. Schmeling; Iris Miraballes; Norma B. Vanasco (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Mild Traumatic Brain Injury and Career Stage Associate with Visible Perivascular Spaces in Special Operations Forces Soldiers - Jacob R. Powell; Xiaopeng Zong; Joshua M. Weinstein; Stephen M. DeLellis; Shawn F. Kane; Gary E. Means; Jason P. Mihalik (Annals of Biomedical Engineering, 2024)

The mentee report: outcomes from implementing a mentorship program for international genetic counseling applicants - Arpita Neogi; Smita K. Rao; Grace Kavanaugh; Tanaya Shroff; Jennifer Kennedy; Michelle F. Jacobs (Journal of Community Genetics, 2024)

DNA barcoding, inter-specific and inter-generic variation studies on South Indian scaly tree ferns ( Cyathea sp.pl.) using chloroplast rbc L gene - Narayanan Janakiraman; Marimuthu Johnson; Jacob Thomas Anne Wincy; Edinardo F. F. Matias; Francisco A. V. dos Santos; Henrique Douglas Melo Coutinho (Plant Biosystems, 2024)

Fate of iron sulfide compounds following simulated wetland sediment deposition - Yadav Sapkota; Jacob F. Berkowitz (Ecological Engineering, 2024)

Investigation of the 2010 rock avalanche onto the regenerated glacier Brenndalsbreen, Norway - Siri H. Engen; Marthe Gjerde; Thomas Scheiber; Gernot Seier; Hallgeir Elvehøy; Jakob Abermann; Atle Nesje; Stefan Winkler; Kristine F. Haualand; Denise C. Rüther; Alexander Maschler; Benjamin A. Robson; et al. (Landslides, 2024)
Rock avalanches onto glaciers are rare in Norway. Here, we examine a rock avalanche that spread onto the regenerated Brenndalsbreen, an outlet glacier from Jostedalsbreen ice cap. The rock avalanche is intriguing in that limited information exists with respect to the exact time of failure, location of detachment area, and preparatory and triggering processes. Based on an analysis of ice stratigraphy and photographic documentation, we assess that the event happened between mid-March and June 4, 2010. A potential triggering factor could have been heavy snow and rainfall combined with above freezing air temperatures on March 18–19, 2010. We use digital terrain models to determine that the detachment area is at an almost vertical rock slope in a narrow gorge above Lower Brenndalsbreen. The deposit volume is estimated to 0.130 ± 0.065 Mm 3 , and the H / L ratio and fahrböschung are 0.45 and 24°, respectively. We apply a Voellmy flow model to confirm the detachment location and volume estimate by producing realistic runout lengths. Although glacial debuttressing may have been a likely preparatory process, the detachment area was exposed for 45–70 years before the rock avalanche occurred. The supraglacial rock avalanche debris was separated into two branches with a distinct melt-out line across the glacier. The debris reached the glacier front in 2019 and 2020, where it started being deposited proglacially while Lower Brenndalsbreen kept receding. The 2010 Brenndalsbreen rock avalanche may not be a unique event, as deposits constituting evidence of an old rock avalanche are currently melting out at the glacier front.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Leaf Shelters Facilitate the Colonisation of Arthropods and Enhance Microbial Diversity on Plants - Danilo F. B. dos Santos; Jacob E. Herschberger; Bijay Subedi; Victoria M. Pocius; Wesley J. Neely; Sasha E. Greenspan; C. Guilherme Becker; Gustavo Q. Romero; Mônica F. Kersch‐Becker (Ecology Letters, 2024)
Shelter‐building insects are important ecosystem engineers, playing critical roles in structuring arthropod communities. Nonetheless, the influence of leaf shelters and arthropods on plant–associated microbiota remains largely unexplored. Arthropods that visit or inhabit plants can contribute to the leaf microbial community, resulting in significant changes in plant–microbe interactions. By artificially constructing leaf shelters, we provide evidence that shelter‐building insects influence not only the arthropod community structure but also impact the phyllosphere microbiota. Leaf shelters exhibited higher abundance and richness of arthropods, changing the associated arthropod community composition. These shelters also altered the composition and community structure of phyllosphere microbiota, promoting greater richness and diversity of bacteria at the phyllosphere. In leaf shelters, microbial diversity positively correlated with the richness and diversity of herbivores. These findings demonstrate the critical role of leaf shelters in structuring both arthropod and microbial communities through altered microhabitats and species interactions.

Overstory and understory resource competition variably influences conversion of introduced conifer plantations to native hardwoods - Jennifer M. Lesko; Joshua L. Sloan; Magnus Löf; Douglass F. Jacobs (Forest Ecology and Management, 2024)

Genetic and other risk factors for pancreatic ductal adenocarcinoma (PDAC) - Michelle F. Jacobs; Elena M. Stoffel (Familial Cancer, 2024)

Common use herbicides increase wetland greenhouse gas emissions - Christine M. Cornish; Olivia F. Johnson; Sheel Bansal; Jacob A. Meier; Ted D. Harris; Jon N. Sweetman (Science of The Total Environment, 2024)

Cycling of fluid-mobile elements through the forearc: Insights from the Cl, B, and Li isotope composition of Costa Rican spring fluids - Jacob P. Helper; Jaime D. Barnes; J. Maarten de Moor; Alejandro Rodríguez; Samuele Agostini; George Segee-Wright; Rudra Chatterjee; Daniel F. Stockli (Geochimica et Cosmochimica Acta, 2024)

Temperature, water travel time, and dissolved organic matter structure river microbial communities in a large temperate watershed - Ted Bambakidis; Byron C. Crump; Byungman Yoon; Ethan D. Kyzivat; Kelly S. Aho; Charles F. Leal; Jennifer H. Fair; Aron Stubbins; Sasha Wagner; Peter A. Raymond; Jacob D. Hosen (Limnology and Oceanography, 2024)
There is growing evidence that the composition of river microbial communities gradually transitions from terrestrial taxa in headwaters to unique planktonic and biofilm taxa downstream. Yet, little is known about fundamental controls on this community transition across scales in river networks. We hypothesized that community composition is controlled by flow‐weighted travel time of water, in combination with temperature and dissolved organic matter (DOM), via similar mechanisms postulated in the Pulse‐Shunt Concept for DOM. Bacterioplankton and biofilm samples were collected at least quarterly for 2 yr at 30 sites throughout the Connecticut River watershed. Among hydrologic variables, travel time was a better predictor of both bacterioplankton and biofilm community structure than watershed area, dendritic distance, or discharge. Among all variables, both bacterioplankton and biofilm composition correlated with travel time, temperature, and DOM composition. Bacterioplankton beta‐diversity was highest at shorter travel times (

Reducing fecal egg count through selective breeding alters dorper lamb response to Haemonchus contortus in an artificial challenge trial - Jacob W. Thorne; Reid Redden; Scott A. Bowdridge; Gabrielle M. Becker; Sarem F. Khilji; Shangqian Xie; Kelsey L. Bentley; Brenda M. Murdoch (Veterinary Parasitology, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

Plasma water T2 detects age-stratified differences in cardiometabolic health among familial CCM patients with Hispanic CCM1 mutation - Jacob Croft; Diana F. Sandoval; David Cistola; Jun Zhang (Metabolic Brain Disease, 2024)

Population expansion and intensification from a Malthus-Boserup perspective: A multiproxy approach in Central Western Argentina - Eva A. Peralta; Jacob Freeman; Adolfo F. Gil (Quaternary International, 2024)

Exploring the adoption of water quality trading as an alternative stormwater regulatory compliance strategy for land development projects: A case study for Roanoke, Virginia - Jacob D. Nelson; Marcus F. Aguilar; Linnea Saby; Kurt Stephenson; Jonathan L. Goodall (Journal of Environmental Management, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Electrochemical reduction of halogenated organic contaminants using carbon-based cathodes: A review - Jacob F. King; William A. Mitch (Critical Reviews in Environmental Science and Technology, 2024)

Effects of sewage sludge application methods on the transport of heavy metals with runoff and their mechanisms - Yuantong Yang; Weixun Feng; Li'an Bao; Lihua Xian; Jie Lu; Daoming Wu; Douglass F. Jacobs; Shucai Zeng (Science of The Total Environment, 2024)

Geothermal Play Fairway Analysis, Part 2: GIS methodology - Jacob DeAngelo; John W. Shervais; Jonathan M. Glen; Dennis Nielson; Sabodh Garg; Patrick F. Dobson; Erika Gasperikova; Eric Sonnenthal; Lee M. Liberty; Drew L. Siler; James P. Evans (Geothermics, 2024)

Senolytic treatment does not mitigate oxidative stress-induced muscle atrophy but improves muscle force generation in CuZn superoxide dismutase knockout mice - Agnieszka K. Borowik; Marcus M. Lawrence; Frederick F. Peelor; Katarzyna M. Piekarz; Abby Crosswhite; Arlan Richardson; Benjamin F. Miller; Holly Van Remmen; Jacob L. Brown (GeroScience, 2024)

A short-interval longitudinal study of associations between psychological distress and hippocampal grey matter in early adolescence - Amanda Boyes; Jacob M. Levenstein; Larisa T. McLoughlin; Christina Driver; Lia Mills; Jim Lagopoulos; Daniel F. Hermens (Brain Imaging and Behavior, 2024)
This study of Australian adolescents ( N = 88, 12-13-years-old) investigated the relationship between hippocampal grey matter volume (GMV) and self-reported psychological distress (K10) at four timepoints, across 12 months. Participants were divided into two groups; those who had K10 scores between 10 and 15 for all four timepoints were categorised as “low distress” (i.e., control group; n = 38), while participants who had K10 scores of 16 or higher at least once over the year were categorised as “moderate-high distress” ( n = 50). Associations were tested by GEE fitting of GMV and K10 measures at the same time point, and in the preceding and subsequent timepoints. Analyses revealed smaller preceding left GMV and larger preceding right GMV were associated with higher subsequent K10 scores in the “moderate-high distress” group. This was not observed in the control group. In contrast, the control group showed significant co-occurring associations (i.e., at the same TP) between GMV and K10 scores. The “moderate-high distress” group experienced greater variability in distress. These results suggest that GMV development in early adolescence is differently associated with psychological distress for those who experience “moderate-high distress” at some point over the year, compared to controls. These findings offer a novel way to utilise short-interval, multiple time-point longitudinal data to explore changes in volume and experience of psychological distress in early adolescents. The results suggest hippocampal volume in early adolescence may be linked to fluctuations in psychological distress.

Connecting coastal wetland microbial community characteristics with soil physicochemical properties across an estuarine salinity and vegetation gradient in Mobile Bay, AL, USA - Eric A. Weingarten; Carina M. Jung; Fiona H. Crocker; Marissa L. Kneer; Nia R. Hurst; Mark A. Chappell; Jacob F. Berkowitz; Karl J. Indest (Frontiers in Marine Science, 2023)
Coastal wetlands provide a variety of ecological functions that sustain biodiverse habitats, serve as barriers to storm surge, regulate biogeochemical cycles, and yield ecosystem goods and services that benefit society. The magnitude of wetland functional delivery varies with geomorphology and landscape position, hydropattern and hydrodynamics, vegetation structure and composition, soil properties, and microbial community assemblages and activities. Here we describe soil physicochemical and microbial diversity along a vegetation and salinity gradient in the Mobile Bay estuary, AL, USA and discuss how these factors feedback on ecosystem characteristics and the delivery of ecological functions. We incorporated microbial biomass, diversity, and community composition into patterns of dominant vegetation cover type and soil properties. Stepwise model selection using permutation tests indicated that vegetation type >> soil horizon > and salinity strongly influenced microbe-soil relationships. The dominant variables governing microbial content were total sulfur concentration in surface soils and nitrate and nitrite (NO x ) for subsurface soils. All biotic and abiotic variables indicated that seasonally inundated forested wetlands represented a distinct microbial biome within the Mobile Bay estuary compared to more frequently flooded and increasingly salt-tolerant Typha , tidal shrub, and Juncus wetland types. Compared with the other wetland types examined for this study, forested wetlands contained ~80% less organic carbon content, ~75% less nitrogen, ~33% less phosphorus, and ~95% less sulfur. Our results show the benefit of incorporating microbial trait data, including metataxonomics, enzymatics, and biomass, with other ecosystem properties such as vegetation and soil characterization data.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Predictors of hippocampal tauopathy in people with and at risk for human immunodeficiency virus infection - Sophie Nader; Esma Karlovich; Etty P. Cortes; Ricardo Insausti; Gregory Meloni; Michelle Jacobs; John F. Crary; Susan Morgello (Journal of NeuroVirology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

In situ carbon uptake of marine macrophytes is highly variable among species, taxa, and morphology - Julian M. Jacobs; Lucian Himes; Florybeth F. La Valle (Frontiers in Marine Science, 2023)
Macroalgae form important coastal ecosystems and are considered to be highly productive, yet individual macrophyte carbon uptake rates are poorly documented and methodologies for in situ assessments of productivity are not well developed. In this study, we employ a 13 C enrichment method in benthic chambers to calculate carbon uptake rates and assess δ 13 C signatures of a large stock of nearshore benthic macroalgae varying in taxa and morphology in Southern California. Our objectives are to 1) identify the variability of carbon uptake and inorganic carbon use among individuals of the same species or morphology, and 2) establish accurate and accessible carbon uptake procedures for coastal benthic primary producers. We found no significant relationship between the observed ranges of environmental factors such as nutrient concentrations, PAR, temperature, conductivity, and productivity rates, suggesting that unique physiological complexions underpin the high variability of carbon uptake and δ 13 C in studied macrophyte samples. We consider three reasons our experimental carbon uptake rates are 3–4 orders of magnitude lower than existing literature, which reports carbon uptake in the same units despite using different methods: 1) underrepresentation of P max , 2) incomplete carbon fractionation corrections, and 3) reduced hydrodynamics within the benthic chambers.

Design strategy for effective passion fruit waste bioconversion with crude fungal enzyme extracts - Ojwang D. Otieno; Obiero George; Mulaa F. Jakim; Midiwo Jacob (Biologia, 2023)

Water activity in subaerial microbial biofilms on stone monuments - A. Tenore; Y. Wu; J. Jacob; D. Bittermann; F. Villa; B. Buttaro; I. Klapper (Science of The Total Environment, 2023)

Genotype-by-environment interaction analysis of dry matter yield of perennial ryegrass cultivars across south-eastern Australia using factor analytic models - Jiashuai Zhu; Khageswor Giri; Noel O. Cogan; Kevin F. Smith; Joe L. Jacobs (Field Crops Research, 2023)

Antibody titers of individuals vaccinated for COVID-19: A systematic review - Aminoddin M Domado; Homobono Jacob F Adaza; Andrea Pauline Nicole C Beltran; Leila M Buenviaje; Catherine D Co; Leira R Combalicer; Shiela May A Corona; John Benedict F Cruz; Maria Adrianne Camille G Dinjotian; Eli Marie S Esperanzate; Shaira Reinalyn G Luna; Ethelbert Justine R Pascua; et al. (Journal of Biosciences, 2023)

P10-12: Toxicological impact of biogenic and anthropogenic secondary organic aerosols - F. Jacob; N. Houzel; L.Y. Alleman; E. Perdrix; S. Antherieu; C. Coeur; P. Genevray; G. Garçon; A. Tomas; J.-M. Lo Guidice (Toxicology Letters, 2023)

New insights into the chemical composition and formation mechanisms of secondary organic aerosols produced in the ozonolysis of limonene - F. Jacob; N. Houzel; P. Genevray; C. Clety; C. Coeur; E. Perdrix; L.Y. Alleman; S. Anthérieu; G. Garçon; G. Dhont; A. Cuisset; J.-M. Lo Guidice; et al. (Journal of Aerosol Science, 2023)

Controls on the composition of dissolved organic matter in treatment wetland source waters of South Florida, USA - Joao Henrique F. Amaral; Jacob R. Gaddy; Thomas S. Bianchi; Todd Z. Osborne; Susan Newman; Jacob Dombrowski; Elise S. Morrison (Ecological Engineering, 2023)

Socio-oceanography: an opportunity to integrate marine social and natural sciences - Ekaterina Popova; Yevgeny Aksenov; Laurent O. Amoudry; Amani Becker; Lucy Bricheno; Jennifer M. Brown; Michael A. Clare; Alan Evans; Claire Evans; Sara E. Fowell; Svetlana Jevrejeva; Zoe Jacobs; et al. (Frontiers in Marine Science, 2023)
Marine natural sciences have been instrumental in helping society understand how ocean systems operate and the threats they face. However, there is a growing realisation that the societal challenges related to the marine environment can only be addressed through more effective integration with all aspects of social sciences. Nevertheless, to date, social sciences remain insufficiently integrated into marine research. Recognising historical weaknesses and drawing on the authors’ own experience of interdisciplinary research, albeit writing primarily from a natural marine science perspective, we propose a series of steps to promote integrated marine research inclusive of strong social science. We suggest that changing the perspectives and attitudes of natural scientists is key. The inherent interconnectivity between the ocean and society ensures that nearly everything we do in the marine natural sciences has the potential to influence and, perhaps address, ongoing and future societal challenges. Consequently, a key challenge for natural scientists is to recognise and communicate this in an accessible manner outside their own disciplines. To attempt to address these issues, we introduce the concept of “Socio-oceanography” which we define as an area of research that takes a “whole system” approach to the marine environment. It focuses on the challenges which require advancement of both natural and social science components, especially on those where the feedbacks between social and natural components are beginning to emerge. Here, we discuss its scope, challenges to its effective application and key steps to catalyse interdisciplinary approaches using this concept.

Mercury accumulation, biomagnification, and relationships to δ13C, δ15N and δ34S of fishes and marine mammals in a coastal Arctic marine food web - David J. Yurkowski; Elena McCulloch; Wesley R. Ogloff; Kelsey F. Johnson; Rémi Amiraux; Niladri Basu; Kyle H. Elliott; Aaron T. Fisk; Steven H. Ferguson; Les N. Harris; Kevin J. Hedges; Kevin Jacobs; et al. (Marine Pollution Bulletin, 2023)

Co-planting of a fast-growing, nitrogen-fixing host tree facilitates regeneration of the root hemiparasitic ‘iliahi (Hawaiian sandalwood) - Emily C. Thyroff; Kyle M.E. Rose; Travis W. Idol; Quinn Moon; Owen T. Burney; Douglass F. Jacobs (Forest Ecology and Management, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Urbanization influences spatiotemporal patterns of roost site selection by black vultures and turkey vultures - Jacob E. Hill; Kenneth F. Kellner; Amanda E. Holland; Bryan M. Kluever; Morgan B. Pfeiffer; Travis L. DeVault; Jerrold L. Belant (Urban Ecosystems, 2023)
Roost locations can be an important contributor to vulture conflicts with humans, but factors influencing roost-site selection at a landscape level remain largely unexplored. Further, there has been little research comparing how these factors vary between nocturnal and diurnal roosting sites. We used remote cameras to document daily variation in vulture use of 21 roosts (20 communication/water towers and 1 natural roost) near Beaufort, South Carolina, USA from October 2019–August 2020. Numbers of vultures on roosts increased with decreasing urban cover and with greater distance to water, but were not influenced by habitat fragmentation or elevation. Roosts surrounded by greater proportions of urban cover were used more often during the day, whereas roosts adjacent to less urban cover were more commonly used at night. We suggest that this relationship results from a greater daytime association with human development, areas that likely provide food and favorable soaring conditions for vultures. Vultures tended to depart nocturnal roosts before sunrise and return within two hours of sunset, indicating that aircraft collision risk resulting from movement around nocturnal roosts would be elevated during these times. Several communication towers routinely had > 100 vultures roosting on them at once, likely contributing to conflict with humans. Our findings reiterate the generalism of these species and their capacity to exploit novel structures for roosting, which has likely contributed to range expansions and resultant increases in human-vulture conflicts over the past several decades.

Multinuclear MRI Reveals Early Efficacy of Stem Cell Therapy in Stroke - Shannon Helsper; Xuegang Yuan; F. Andrew Bagdasarian; Jacob Athey; Yan Li; Cesario V. Borlongan; Samuel C. Grant (Translational Stroke Research, 2023)

Target sequence capture data shed light on the deeper evolutionary relationships of subgenus Chamaecerasus in Lonicera (Caprifoliaceae) - Qing-Hui Sun; Diego F. Morales-Briones; Hong-Xin Wang; Jacob B. Landis; Jun Wen; Hua-Feng Wang (Molecular Phylogenetics and Evolution, 2023)

Combined addition of bagasse and zeolite stabilizes potentially toxic elements in sewage sludge compost and improves Eucalyptus urophylla seedling growth - Shuangshuang Chu; Lihua Xian; Nan Zhao; Can Lai; Wenjun Yang; Jing Wang; Mandi Long; Dandan Liao; Jianhui Ouyang; Zhonglin Wang; Douglass F. Jacobs; Shucai Zeng (Forest Ecology and Management, 2023)

Reintroduction of at-risk forest tree species using biotechnology depends on regulatory policy, informed by science and with public support - Douglass F. Jacobs; R. Kasten Dumroese; Andrea N. Brennan; Faith T. Campbell; Anna O. Conrad; Jason A. Delborne; Sara Fitzsimmons; David Flores; Christian P. Giardina; Leigh Greenwood; Juan A. Martín; Scott A. Merkle; et al. (New Forests, 2023)
Introduced pests (insects and pathogens) have rapidly increased the numbers of at-risk native forest tree species worldwide. Some keystone species have been functionally extirpated, resulting in severe commercial and ecological losses. When efforts to exclude or mitigate pests have failed, researchers have sometimes applied biotechnology tools to incorporate pest resistance in at-risk species to enable their reintroduction. Often erroneously equated solely with genetic engineering, biotechnology also includes traditional and genome informed breeding—and may provide a holistic approach toward applying genomic-based information and interventions to increase tree species’ pest resistance. Traditional tree breeding is responsible for successes to date, but new technologies offer hope to increase the efficiency of such efforts. Remarkable recent progress has been made, and for some at-risk species, novel biotechnological advances put reintroduction within reach. The high costs of reintroduction of at-risk species at necessary scale, however, will initially limit the pursuit to a few species. Successful deployment of pest resistant material may require improved species-specific knowledge and should integrate into and leverage existing reforestation systems, but these operations are sometimes rare where pest threats are greatest. While use of some biotechnologies, such as traditional tree breeding, are commonplace, others such as genetic engineering are controversial and highly regulated, yet may be the only viable means of achieving reintroduction of some at-risk species. Efforts to modify policy toward allowing the use of appropriate biotechnology, especially genetic engineering, have lagged. Provided that risk-benefits are favorable, policy is likely to follow with public opinion; in some countries, society is now increasingly open to using available biotechnologies. Continued engagement using the most recent advances in social science to build public trust, combined with a science-based collaboration among land managers and regulators, will generate the collective momentum needed to motivate policymakers to act rapidly given the speed at which forest health threats unfold and the large areas they affect.

A framework for establishing a rapid ‘Ōhi‘a death resistance program - Blaine C. Luiz; Christian P. Giardina; Lisa M. Keith; Douglass F. Jacobs; Richard A. Sniezko; Marc A. Hughes; James B. Friday; Philip Cannon; Robert Hauff; Kainana Francisco; Marian M. Chau; Nicklos Dudley; et al. (New Forests, 2023)
Metrosideros polymorpha Gaud. (‘ōhi‘a) is the most abundant native forest tree in Hawai‘i and a keystone species of cultural, ecological, and economic importance. ‘Ōhi‘a forests, particularly on Hawaiʻi Island, are being severely impacted by Rapid ‘Ōhi‘a Death (ROD), which is caused by the fungal pathogens Ceratocystis lukuohia and C. huliohia . ROD is characterized by branch dieback, crown wilting, and mortality. Initial disease resistance screening of four varieties of M. polymorpha with C. lukuohia demonstrated that varieties may differ in susceptibility. Several survivors of field or screening-based infections still exist, providing strong impetus for the establishment of the ‘Ōhiʻa Disease Resistance Program (ʻŌDRP). Here, we outline a framework for guiding the ʻŌDRP throughout the process of identifying and developing ROD resistance in M. polymorpha and, possibly, all Hawaiian Metrosideros species. Core ʻŌDRP projects include: (1) evaluating and operationalizing methods for greenhouse-based production and screening of test plants; (2) greenhouse screening of seedlings and rooted cuttings sampled from native Metrosideros throughout Hawaiʻi; (3) establishing field trials to validate results from greenhouse assays; (4) understanding environmental and genetic drivers of resistance to characterize the durability of resistance to ROD; (5) developing remote sensing and molecular methods to rapidly detect ROD-resistant individuals; and (6) conducting breeding trials to improve the degree and durability of ROD resistance. Ultimately, the ʻŌDRP seeks to produce ROD-resistant material for the perpetuation of M. polymorpha across Hawai‘i, with the goal of preserving the ecology, culture, and communities that are dependent on this tree species.

Perceptions of land managers towards using hybrid and genetically modified trees - Andrea N. Brennan; Zhao Ma; Douglass F. Jacobs (New Forests, 2023)
Hybridization and genetic modification are potential methods for incorporation of stress tolerance being explored to support some at-risk tree species. However, many concerns, both ecological and economic, have been identified in using these biotechnologies, such as potential for invasiveness or high cost. There is limited information on perceptions towards hybrid and genetically modified (GM) trees, particularly from individuals responsible for widescale tree management. An online survey was administered to land managers in Indiana, USA to gauge perceptions to hybrid and GM trees, and current hybrid tree use. Land managers had stronger concern for ecological, rather than economic, issues, with potential for invasiveness being strongest. Agreement was highest for using the tree types for conservation and restoration of at-risk species and production purposes. However, perceptions varied by characteristics such as concern type, age, and land type managed. Ecological concern and land type managed most strongly predicted hybrid use. Overall, the majority of land managers agreed, rather than disagreed, with a variety of potential hybrid and GM tree advantages and purposes. Thus, results indicate that if these biotechnologies are deemed appropriate for supporting at-risk species, the majority of land managers in Indiana might be agreeable to such recommendations from researchers. However, it was also clear that despite this, most respondents concurrently had strong ecological concerns about suitability as a native species replacement. To address this, it is essential that these tree types be thoroughly vetted, and land managers be actively engaged in the process, as this population would ultimately be responsible for any widescale implementation of hybrid and GM trees.

A retrospective cohort study of genetic referral and diagnosis of Lynch syndrome in patients with cutaneous sebaceous lesions - Meera Kattapuram; Christina Shabet; Sarah Austin; Michelle F. Jacobs; Erika Koeppe; Emily H. Smith; Lori Lowe; Tobias Else; Kelly B. Cha (Familial Cancer, 2023)

Morphological and transcriptional effects of crude oil and dispersant exposure on the marine sponge Cinachyrella alloclada - Yvain Desplat; Jacob F. Warner; Emily J. Blake; Nidhi Vijayan; Marie Cuvelier; Patricia Blackwelder; Jose V. Lopez (Science of The Total Environment, 2023)

Use of ozonated sunflower oil in the treatment of infectious endometritis in mares - Naiane F Oliveira; Camila S Ferreira; Luis F Silva; Isadora P Santos; Julio C Jacob; Bruno A Penna; Aline E Pinna (Journal of Equine Veterinary Science, 2023)

Exploratory analysis of machine learning techniques in the Nevada geothermal play fairway analysis - Connor M. Smith; James E. Faulds; Stephen Brown; Mark Coolbaugh; Jacob DeAngelo; Jonathan M. Glen; Erick R. Burns; Drew L. Siler; Sven Treitel; Eli Mlawsky; Michael Fehler; Chen Gu; et al. (Geothermics, 2023)

Correction to: Documentation of Iron Monosulfide Improves Hydric soil Identification in Semi-Arid Wetlands - Chelsea Duball; Karen Vaughan; Angela Elg; Andy Steinert; Jacob F. Berkowitz (Wetlands, 2023)

Zoning strategies for managing outbreaks of alien plant pests in the European Union: a review - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Roel P. J. Potting; Donato Boscia; Antonio Vicent; Alan MacLeod; Wopke van der Werf (Journal of Pest Science, 2023)
Managing outbreaks of alien plant pests is key to preserving biodiversity and safeguarding crop production. Zoning strategies are applied by plant health authorities to tailor measures to the risk of spread in relation to distance from the outbreak epicentre and the biology of the pest. Here we synthesize information on outbreak management to evaluate the diversity and consistency of such approaches. We collected information on the zoning strategies of 121 outbreaks of 25 plant pests in the European Union (EU). According to the organism’s presence and the measures applied, five zones were distinguished: an infested zone (83% of cases), a buffer zone (76%), a clear-cutting zone (28%), an eradication zone (1%) and a containment zone (1%). Infested zones and buffer zones were adjacent non-overlapping zones, while the clear-cutting zone, eradication zone or containment zone was within either the infested zone or buffer zone. A combination of infested and buffer zones was used in 51% of recorded cases. Measures differed within different zones. Destruction of infested plants in the infested zone was done in 78% of the cases, while surveillance was always applied in the buffer zone. Regulation of an organism at EU level led to a convergence of zoning strategies applied by different member states. Regulations often prescribed the greatest widths used before regulations were issued. Further analyses are needed to explore the efficacy of different strategies including the costs of each strategy. Such analyses should combine insight from practice with bio-economic modelling.

Aboveground wetland vegetation growth responses to simulated sediment diversion inundation scenarios - Ashleigh N. Lambiotte; Jacob F. Berkowitz; Glenn M. Suir; Jonathan M. Willis (Ecological Engineering, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Combined application of sewage sludge, bagasse, and molybdenum tailings ameliorates rare earth mining wasteland soil - Jiayi Feng; Yuantong Yang; Kejin Ruan; Daoming Wu; Yanggui Xu; Douglass F. Jacobs; Shucai Zeng (Journal of Soils and Sediments, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Documentation of iron Monosulfide Improves Hydric soil Identification in Semi-arid Wetlands - Chelsea Duball; Karen Vaughan; Angela Elg; Andy Steinert; Jacob F. Berkowitz (Wetlands, 2023)

Long-term growing season aridity and grazing seasonality effects on perennial grass biomass in a Chihuahuan Desert rangeland - Sophia N. Lasché; Ryan W.R. Schroeder; Matthew M. McIntosh; Jacob E. Lucero; Sheri A. Spiegal; Micah P. Funk; Reldon F. Beck; Jerry L. Holechek; Akasha M. Faist (Journal of Arid Environments, 2023)

Towards stability of food production and farm income in a variable climate - Caroline Harkness; Francisco J. Areal; Mikhail A. Semenov; Nimai Senapati; Ian F. Shield; Jacob Bishop (Ecological Economics, 2023)

Vaping THC-O Acetate: Potential for Another EVALI Epidemic - Neal L. Benowitz; Christopher Havel; Peyton Jacob; Donal F. O’Shea; Dan Wu; Jefferson Fowles (Journal of Medical Toxicology, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Controls on the frequency content of near-source infrasound at open-vent volcanoes: a case study from Volcán Villarrica, Chile - Bryan B. Rosenblatt; Jeffrey B. Johnson; Jacob F. Anderson; Keehoon Kim; Scott J. Gauvain (Bulletin of Volcanology, 2022)

Confined Tensile Testing of Porous Sandstone - Ali Tarokh; Jacob D. Sharpe; Joseph F. Labuz (Rock Mechanics and Rock Engineering, 2022)

Environmental conditions in the nursery regulate root system development and architecture of forest tree seedlings: a systematic review - Andrei Toca; Ehren Moler; Andrew Nelson; Douglass F. Jacobs (New Forests, 2022)

Forward to the second special seedling root development - Diane L. Haase; Douglass F. Jacobs (New Forests, 2022)

Root system adaptations represent untapped opportunities for forest tree seedling improvement - Ehren R. V. Moler; Andrei Toca; Douglass F. Jacobs; Andrew S. Nelson (New Forests, 2022)

Particle Property Characterization and Data Curation for Effective Powder Property Modeling in the Pharmaceutical Industry - Robert C. Wadams; Ilgaz Akseli; Jacob Albrecht; Ana P. Ferreira; John F. Gamble; Michael Leane; Stephen Thomas; Yue Schuman; Lauren Taylor; Mike Tobyn (AAPS PharmSciTech, 2022)

Geomorphology and initiation mechanisms of the 2020 Haines, Alaska landslide - Margaret M. Darrow; Victoria A. Nelson; Michael Grilliot; Joseph Wartman; Aaron Jacobs; James F. Baichtal; Cindy Buxton (Landslides, 2022)
In early December 2020, an atmospheric river (AR) and rain-on-snow (ROS) event impacted the Haines, Alaska area, resulting in record-breaking rainfall and snowmelt that caused flooding and dozens of mass movement events. We consider the AR—a one-in-500-year event—as the trigger for the devastating Beach Road Landslide (BRLS), which destroyed or damaged four residences and took the lives of two people. The BRLS started as a debris avalanche and transitioned into a debris flow, with a total approximate landslide volume of 187,100 m 3 . Geomorphic analysis using lidar data identified evidence of paleo-landslides and displaced masses of rock, one of which served as the source area for the BRLS. Significant structural features in the weak ultramafic bedrock defined the head scarp area and formed the failure plane. This study illustrates the importance of identifying pre-existing landslide features and source areas likely to produce future landslides. As an increase in ROS events is projected for Southeast Alaska with warmer and wetter winters, we recommend the development of an AR scale coupled with geological information for the region, to enhance warnings to residents in landslide-prone areas.

Performance of Semi-passive Systems for the Biological Treatment of High-As Acid Mine Drainage: Results from a Year of Monitoring at the Carnoulès Mine (Southern France) - C. Diaz-Vanegas; C. Casiot; L. Lin; L. De Windt; M. Héry; A. Desoeuvre; O. Bruneel; F. Battaglia-Brunet; J. Jacob (Mine Water and the Environment, 2022)

Confluences and land cover as agents of change: habitat change modifies the movement and assemblage stability of headwater fishes - Joshua P. Hubbell; Jacob F. Schaefer (Urban Ecosystems, 2022)

Determination of Tri halo methanes in indoor swimming pools, Kuwait and development of health risk index - D. R. Samayamanthula; M. E. Bhatti; N. F. Al-Enazi; Z. A. J. Rashid; S. A. Al-Kandari; H. Jacob (International Journal of Environmental Science and Technology, 2022)

Biochemical analysis of novel NAA10 variants suggests distinct pathogenic mechanisms involving impaired protein N-terminal acetylation - Nina McTiernan; Lisbeth Tranebjærg; Anna S. Bjørheim; Jacob S. Hogue; William G. Wilson; Berkley Schmidt; Melissa M. Boerrigter; Maja L. Nybo; Marie F. Smeland; Zeynep Tümer; Thomas Arnesen (Human Genetics, 2022)
NAA10 is the catalytic subunit of the N-terminal acetyltransferase complex, NatA, which is responsible for N-terminal acetylation of nearly half the human proteome. Since 2011, at least 21 different NAA10 missense variants have been reported as pathogenic in humans. The clinical features associated with this X-linked condition vary, but commonly described features include developmental delay, intellectual disability, cardiac anomalies, brain abnormalities, facial dysmorphism and/or visual impairment. Here, we present eight individuals from five families with five different de novo or inherited NAA10 variants. In order to determine their pathogenicity, we have performed biochemical characterisation of the four novel variants c.16G>C p.(A6P), c.235C>T p.(R79C), c.386A>C p.(Q129P) and c.469G>A p.(E157K). Additionally, we clinically describe one new case with a previously identified pathogenic variant, c.384T>G p.(F128L). Our study provides important insight into how different NAA10 missense variants impact distinct biochemical functions of NAA10 involving the ability of NAA10 to perform N-terminal acetylation. These investigations may partially explain the phenotypic variability in affected individuals and emphasise the complexity of the cellular pathways downstream of NAA10.

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Correction to: Outcomes of retesting in patients with previously uninformative cancer genetics evaluations - Shenin A. Sanoba; Erika S. Koeppe; Michelle F. Jacobs; Elena M. Stoffel (Familial Cancer, 2022)

Outcomes of retesting in patients with previously uninformative cancer genetics evaluations - Shenin A. Sanoba; Erika S. Koeppe; Michelle F. Jacobs; Elena M. Stoffel (Familial Cancer, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Effect of Various Local Anthropogenic Impacts on the Diversity of Coral Mucus-Associated Bacterial Communities - Emad I. Hussein; Abdul-Salam F. Juhmani; Jacob H. Jacob; Mahmoud A. Telfah; Mutaz A. Abd Al-razaq; Fuad A. Al-Horani; Mazhar Salim Al Zoubi; Hanan I. Malkawi (Journal of Marine Science and Engineering, 2022)
The global continued decline in coral reefs is intensifying the need to understand the response of corals to local environmental stressors. Coral-associated bacterial communities have been suggested to have a swift response to environmental pollutants. This study aims to determine the variation in the bacterial communities associated with the mucus of two coral species, Pocillopora damicornis (Linnaeus, 1758) and Stylophora pistillata (Esper, 1792), and the coral-surrounding seawater from three areas exposed to contamination at the Jordanian coast of the Gulf of Aqaba (Red Sea), and also explores the antibacterial activity of these bacteria. Corals were collected from three contaminated zones along the coast, and the bacteria were quantified and identified by conventional morphological and biochemical tests, as well as 16S rRNA gene sequencing. The average number of bacteria significantly varied among the coral mucus from the sampling zones and between the coral mucus and the surrounding seawater. The P. damicornis mucus-associated bacterial community was dominated by members of the classes Gammaproteobacteria, Cytophagia, and Actinomycetia, while the mucus of S. pistillata represented higher bacterial diversity, with the dominance of the bacterial classes Gammaproteobacteria, Actinomycetia, Alphaproteobacteria, and Bacilli. The effects of local anthropogenic impacts on coral mucus bacterial communities were represented in the increased abundance of bacterial species related to coral diseases. Furthermore, the results demonstrated the existence of bacterial isolates with antibacterial activity that possibly acted as a first line of defense to protect and maintain the coral host against pathogens. Indeed, the dynamics of coral-associated microbial communities highlight the importance of holistic studies that focus on microbial interactions across the coral reef ecosystem.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

Demographic consequences of mutualism disruption: Browsing and big‐headed ant invasion drive acacia population declines - Brandon R. Hays; Corinna Riginos; Todd M. Palmer; Daniel F. Doak; Benard C. Gituku; Nelly J. Maiyo; Samuel Mutisya; Simon Musila; Jacob R. Goheen (Ecology, 2022)
Across the globe, biological invasions have disrupted mutualisms, producing reverberating consequences for ecosystems. Although invasive species frequently trigger mutualism disruptions, few studies have quantified the demographic mechanisms by which mutualism breakdown may generate population effects. In a Kenyan savanna, the invasive big‐headed ant ( Pheidole megacephala ) has disrupted a foundational mutualism between the monodominant whistling‐thorn tree ( Acacia drepanolobium ) and native ants ( Crematogaster spp.) that deter browsing by large mammalian herbivores. We conducted experiments to quantify the demographic consequences of this mutualism disruption in the presence and absence of large mammalian herbivores. Invasion by P. megacephala exacerbated population declines of A. drepanolobium , primarily through decreased survival and reproduction of adult trees. However, these fitness reductions were small compared to those resulting from the presence of large mammalian herbivores, which negatively impacted growth and survival. Contrary to expectation, the expulsion of metabolically costly Crematogaster mutualists by P. megacephala did not result in higher population growth rates for trees protected from large mammalian herbivores. Our results suggest that invasive P. megacephala may impose a direct metabolic cost to trees exceeding that of native mutualists while providing no protection from browsing by large mammalian herbivores. Across landscapes, we expect that invasion by P. megacephala will reduce A. drepanolobium populations, but that the magnitude and demographic pathways of this effect will hinge on the presence and abundance of browsers.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Palaeoceanographic changes in the late Pliocene promoted rapid diversification in pelagic seabirds - Joan Ferrer Obiol; Helen F. James; R. Terry Chesser; Vincent Bretagnolle; Jacob González‐Solís; Julio Rozas; Andreanna J. Welch; Marta Riutort (Journal of Biogeography, 2022)
Aim Palaeoceanographic changes can act as drivers of diversification and speciation, even in highly mobile marine organisms. Shearwaters are a group of globally distributed and highly mobile pelagic seabirds. Despite a recent well‐resolved phylogeny, shearwaters have controversial species limits, and show periods of both slow and rapid diversification. Here, we explore the role of palaeoceanographic changes on shearwaters' diversification and speciation. We investigate shearwater biogeography and the evolution of a key phenotypic trait, body size, and we assess the validity of their current taxonomy. Location Worldwide. Taxa Shearwaters (Order Procellariiformes, Family Procellariidae, Genera Ardenna , Calonectris and Puffinus ). Methods We generated genomic (ddRAD) data to infer a time‐calibrated species tree for the shearwaters. We estimated ancestral ranges and evaluated the roles of founder events, vicariance and surface ocean currents in driving diversification. We performed phylogenetic generalised least squares to identify potential predictors of variability in body size along the phylogeny. To assess the validity of the current taxonomy, we analysed genomic patterns of recent shared ancestry and differentiation among shearwater taxa. Results We identified a period of high dispersal and rapid speciation during the Late Pliocene–early Pleistocene. Species dispersal appears to be favoured by surface ocean currents, and founder events are supported as the main mode of speciation in these highly mobile pelagic seabirds. Body mass shows significant associations with life strategies and local conditions. The current taxonomy shows some incongruences with the patterns of genomic divergence. Main Conclusions A reduction of neritic areas during the Pliocene seems to have driven global extinctions of shearwater species, followed by a subsequent burst of speciation and dispersal probably promoted by Plio‐Pleistocene climatic shifts. Our findings extend our understanding on the drivers of speciation and dispersal of highly mobile pelagic seabirds and shed new light on the important role of palaeoceanographic events.

Water-stained leaves: formation and application as a field indicator of wetland hydrology - Jacob F. Berkowitz; Jason P. Pietroski (Wetlands, 2021)
Wetland delineations conducted in the United States utilize field indicators as proxy measures of the presence or absence of wetland hydrology. Water-stained leaves provide a practical, qualitative field indicator of wetland hydrology; however, the formation of water-stained leaves has not been elucidated. In response, leaves from six tree species were examined under five treatments to investigate the water-staining process and concomitant timeframes. Results indicate that leaf staining occurred within 14-21 days of continuous exposure to wetland waters and sediment under both laboratory and field conditions. Leaf staining was characterized by readily observable shifts in leaf color (i.e., decreasing Munsell hue, value, and chroma) causing the leaves to appear very dark or black. No color shifts associated with leaf staining occurred in treatments exposed to upland conditions. The timeframe associated with leaf staining corresponds with established wetland hydrology criteria requiring a minimum hydroperiod of 14 consecutive days of soil saturation, flooding, or ponding. Leaves exposed to wetland waters and sediment underwent color shifts significantly faster and to a greater extent than leaves inundated with deionized water, likely as a result of increased microbial abundance and the presence of anaerobic conditions in the simulated wetland treatments. Results suggest that water-stained leaves 1) are a useful and reliable wetland hydrology field indicator for wetland delineation purposes, 2) may provide a proxy measure of wetland hydroperiod, and 3) Munsell color measurements can help differentiate between leaves exposed to wetland and upland conditions.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Correction to: The effect of different logging regimes on the ecomorphological structure of stream fish assemblages in the Brazilian Amazon - Laís L. Jacob; Bruno S. Prudente; Luciano F. A. Montag; Rogério R. Silva (Hydrobiologia, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

FMRF-related peptides in Aedes aegypti midgut: neuromuscular connections and enteric nervous system - Raquel S. M. Godoy; Renata C. Barbosa; Thamara F. Procópio; Breno A. Costa; Marcelo Jacobs-Lorena; Gustavo F. Martins (Cell and Tissue Research, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Physiological responses to maximal 4 s sprint interval cycling using inertial loading: the influence of inter-sprint recovery duration - Emre Vardarli; Remzi Satiroglu; Jacob R. Allen; Ryan Bjellquist-Ledger; Heath M. Burton; Edward F. Coyle (European Journal of Applied Physiology, 2021)

Analysis of shark NCR3 family genes reveals primordial features of vertebrate NKp30 - Allison Kinlein; Morgan E. Janes; Jacob Kincer; Tereza Almeida; Hanover Matz; Jianxin Sui; Michael F. Criscitiello; Martin F. Flajnik; Yuko Ohta (Immunogenetics, 2021)

Density-dependent plant growth drives grazer stimulation of aboveground net primary production in Yellowstone grasslands - Jacob F. Penner; Douglas A. Frank (Oecologia, 2021)

Species interactions alter the selection of thermal environment in a coral reef fish - Tiffany J. Nay; Jacob L. Johansen; Jodie L. Rummer; John F. Steffensen; Andrew S. Hoey (Oecologia, 2021)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Ruling out underlying infection in 200 presumed aseptic knee and hip revision arthroplasties using a multiplex PCR system - Anouk M. E. Jacobs; Petra J. C. Heesterbeek; Frans A. T. Bovendeert; Saskia Susan; Jacques F. Meis; Jon H. M. Goosen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Trace element and isotopic zoning of garnetite veins in amphibolitized eclogite, Franciscan Complex, California, USA - Alicia M. Cruz-Uribe; F. Zeb Page; Emilie Lozier; Maureen D. Feineman; Thomas Zack; Regina Mertz-Kraus; Dorrit E. Jacob; Kouki Kitajima (Contributions to Mineralogy and Petrology, 2021)

Is a colorectal neoplasm diagnosis a trigger to change dietary and other lifestyle habits for persons with Lynch syndrome? A prospective cohort study - Jesca G. M. Brouwer; Merel Snellen; Tanya M. Bisseling; Jan Jacob Koornstra; Hans F. A. Vasen; Ellen Kampman; Fränzel J. B. van Duijnhoven (Familial Cancer, 2021)
A cancer diagnosis is suggested to be associated with changes in dietary and lifestyle habits. Whether this applies to persons with familial cancer, such as Lynch syndrome (LS) is unknown. We investigated whether a colorectal neoplasm (CRN) diagnosis in persons with LS is associated with changes in dietary and lifestyle habits over time. We used data of confirmed LS mutation carriers from the GEOLynch study, a prospective cohort study. Information on dietary intake and lifestyle habits was collected with a validated semi-quantitative food frequency questionnaire and a general questionnaire administered at baseline (2006–2008) and follow-up (2012–2017). Participants’ medical records were used to identify CRN diagnoses. Changes in dietary and lifestyle habits in the CRN and the no-CRN group were compared using multivariable linear regression models for continuous variables and cross-tables with percentage change at follow-up compared with baseline for categorical variables. Of the 324 included participants, 146 developed a CRN (CRN group) between baseline and follow-up, while 178 did not (no-CRN group). Smoking cessation was more often reported in the CRN than in the no-CRN group (41.4% vs. 35.0%). There were no differences in changes of energy intake, alcohol, red meat, processed meat, dairy, fruit, vegetables and dietary fiber consumption, BMI, physical activity and NSAID use. Apart from a potentially higher likelihood of smoking cessation, we found little evidence that a CRN diagnosis is associated with changes in lifestyle habits in persons with LS.

The effect of different logging regimes on the ecomorphological structure of stream fish assemblages in the Brazilian Amazon - Laís L. Jacob; Bruno S. Prudente; Luciano F. A. Montag; Rogério R. Silva (Hydrobiologia, 2021)

Regulate or tolerate: Thermal strategy of a coral reef flat resident, the epaulette shark, Hemiscyllium ocellatum - Tiffany J Nay; Rohan J Longbottom; Connor R Gervais; Jacob L Johansen; John F Steffensen; Jodie L Rummer; Andrew S Hoey (Journal of Fish Biology, 2021)
Highly variable thermal environments, such as coral reef flats, are challenging for marine ectotherms and are thought to invoke the use of behavioural strategies to avoid extreme temperatures and seek out thermal environments close to their preferred temperatures. Common to coral reef flats, the epaulette shark ( Hemiscyllium ocellatum ) possesses physiological adaptations to hypoxic and hypercapnic conditions, such as those experienced on reef flats, but little is known regarding the thermal strategies used by these sharks. We investigated whether H. ocellatum uses behavioural thermoregulation ( i.e ., movement to occupy thermally favourable microhabitats) or tolerates the broad range of temperatures experienced on the reef flat. Using an automated shuttlebox system, we determined the preferred temperature of H. ocellatum under controlled laboratory conditions and then compared this preferred temperature to 6 months of in situ environmental and body temperatures of individual H. ocellatum across the Heron Island reef flat. The preferred temperature of H. ocellatum under controlled conditions was 20.7 ± 1.5°C, but the body temperatures of individual H. ocellatum on the Heron Island reef flat mirrored environmental temperatures regardless of season or month. Despite substantial temporal variation in temperature on the Heron Island reef flat (15–34°C during 2017), there was a lack of spatial variation in temperature across the reef flat between sites or microhabitats. This limited spatial variation in temperature creates a low‐quality thermal habitat limiting the ability of H. ocellatum to behaviourally thermoregulate. Behavioural thermoregulation is assumed in many shark species, but it appears that H. ocellatum may utilize other physiological strategies to cope with extreme temperature fluctuations on coral reef flats. While H. ocellatum appears to be able to tolerate acute exposure to temperatures well outside of their preferred temperature, it is unclear how this, and other, species will cope as temperatures continue to rise and approach their critical thermal limits. Understanding how species will respond to continued warming and the strategies they may use will be key to predicting future populations and assemblages.

Effect of acorn size on survival and growth of Quercus suber L. seedlings under water stress - Taher Mechergui; Marta Pardos; Douglass F. Jacobs (European Journal of Forest Research, 2021)

Chromite chemistry of a massive chromitite seam in the northern limb of the Bushveld Igneous Complex, South Africa: correlation with the UG-2 in the eastern and western limbs and evidence of variable assimilation of footwall rocks - Malose M. Langa; Pedro J. Jugo; Matthew I. Leybourne; Danie F. Grobler; Jacob Adetunji; Henrik Skogby (Mineralium Deposita, 2021)
The Bushveld Igneous Complex (BIC) is known for its laterally extensive platinum group element–bearing layers, the most famous being the Merensky Reef and the UG-2 chromitite in the eastern and western limbs of the complex. In the northern limb, the Platreef mineralization and a thick chromitite seam below it (referred to as the “UG-2 equivalent” or UG-2E) have been proposed to be the stratigraphic equivalents of the Merensky Reef and the UG-2, respectively. In this study, we compare a suite of UG-2E samples from the Turfspruit project with a UG-2 reference suite from the western limb using petrography, electron probe microanalysis, laser ablation-inductively coupled plasma-mass spectrometry, and Mössbauer spectroscopy. The results show that (a) in Mg# vs. Cr# diagrams, UG-2E chromites have a distinct compositional field; however, when samples of similar chromite modal abundance (≥ 80%) are used, the UG-2E chromites overlap the field that characterizes UG-2 chromites; (b) the UG-2E is more variable in chromite modal abundance than the UG-2; and (c) variations in Mg# and Fe 3+ /ΣFe in the UG-2E indicate contamination of the magma by metasedimentary rocks of the Duitschland Formation (Transvaal Supergroup) during emplacement, followed by partial re-equilibration of chromite grains with a trapped melt. Thus, we conclude that for chromite modes higher than 80%, the chromite composition retains enough information to allow correlation and that the UG-2E in the northern limb is very likely the UG-2 chromitite.

Germline variants discovered in lymphoma patients undergoing tumor profiling: a case series - Anthony J. Scott; Molly C. Tokaz; Michelle F. Jacobs; Arul M. Chinnaiyan; Tycel J. Phillips; Ryan A. Wilcox (Familial Cancer, 2021)

Wetland Vegetation Response to Groundwater Pumping and Hydrologic Recovery - Megan K. Bartholomew; Christopher J. Anderson; Jacob F. Berkowitz (Wetlands, 2020)
An investigation of wetland vegetation response to groundwater alteration was conducted at the J.B. Starkey Wilderness Park, a large municipal wellfield in the area of west Florida, USA. Decades of historic groundwater withdrawal had created a gradient of impacted wetlands on the wellfield, after which time the groundwater pumping rates were reduced. Nineteen cypress dome wetlands were grouped, based on their hydrologic histories, as either most-altered (least inundation), marginally-altered (intermediate inundation), or least-altered (near-normal inundation). Annual species–level monitoring data were used to evaluate understory plant community response to the hydrologic recovery that resulted from reduced groundwater pumping. Species richness, cover, prevalence index (PI), and species importance percentages were assessed during pre- (2005–2007) and post- (2012–2014) hydrologic recovery periods. The vegetation in marginally- and most-altered wetlands responded to hydrologic recovery with increased species richness and lower PI values (i.e., greater hydrophytic character). However, species importance percentages indicated greater variation in the recovery of most-altered wetlands, where species composition often remained different from least-altered wetlands. Although reductions in groundwater pumping caused sufficient passive hydrologic recovery to elicit a vegetation response, further reductions and/or more time may be needed before the vegetation of some altered wetlands can become comparable to that of least-impacted wetlands.

Wetland Functional Responses to Prolonged Inundation in the Active Mississippi River Floodplain - Jaybus J. Price; Jacob F. Berkowitz (Wetlands, 2020)
The Mississippi River experienced historic flooding during 2019, inducing >150 days of floodplain wetland inundation. We evaluated flood effects using repeated measures of hydrogeomorphic (HGM) wetland assessment variables prior to the flood (October 2018), immediately post-flood (August 2019) and one year after initial assessment (October 2019). The flood had little/no impact on 11 of 13 assessment variables, but altered the abundance of woody debris and forest floor litter. Immediately after the flood, these changes decreased the functional capacity of wetlands to 1) detain floodwater (mean − 9.7% reduction) and 2) precipitation (−17.3%); 3) cycle nutrients (−7.5%); and export organic carbon (−23.8%). Subsequent sampling documented the detain precipitation function returning to pre-flood conditions. The export organic carbon function also improved, yet remained below pre-flood levels. Other functions will likely require additional recovery time due to the persistence of accumulated excess woody debris. Across all sample intervals, floodplain wetlands displayed high wetland function capacities and appear resilient to surface water inundation. This analysis highlights the utility of the HGM assessment to detect responses to changing environmental conditions over short time intervals. The study also emphasizes the need to incorporate metrics with appropriate impact-response characteristics when developing and implementing ecological assessments.

The Effect of Muscle Activation on Head Kinematics During Non-injurious Head Impacts in Human Subjects - Kristen A. Reynier; Ahmed Alshareef; Erin J. Sanchez; Daniel F. Shedd; Samuel R. Walton; Nicholas K. Erdman; Benjamin T. Newman; J. Sebastian Giudice; Michael J. Higgins; James R. Funk; Donna K. Broshek; Thomas J. Druzgal; et al. (Annals of Biomedical Engineering, 2020)

Modular timer networks: abdominal interneurons controlling the chirp and pulse pattern in a cricket calling song - Pedro F. Jacob; Berthold Hedwig (Journal of Comparative Physiology A, 2020)
Chirping male crickets combine a 30 Hz pulse pattern with a 3 Hz chirp pattern to drive the rhythmic opening-closing movements of the front wings for sound production. Lesion experiments suggest two coupled modular timer-networks located along the chain of abdominal ganglia, a network in A3 and A4 generating the pulse pattern, and a network organized along with ganglia A4–A6 controlling the generation of the chirp rhythm. We analyzed neurons of the timer-networks and their synaptic connections by intracellular recordings and staining. We identified neurons spiking in phase with the chirps and pulses, or that are inhibited during the chirps. Neurons share a similar “gestalt”, regarding the position of the cell body, the dendritic arborizations and the contralateral ascending axon. Activating neurons of the pulse-timer network elicits ongoing motor activity driving the generation of pulses; this activity is not structured in the chirp pattern. Activating neurons of the chirp-timer network excites pulse-timer neurons; it drives the generation of chirps and during the chirps the pulse pattern is produced. Our results support the hypothesis that two modular networks along the abdominal ganglion chain control the cricket calling song, a pattern generating network in the mesothoracic ganglion may not be required.

On-Field Performance of an Instrumented Mouthguard for Detecting Head Impacts in American Football - Lee F. Gabler; Samuel H. Huddleston; Nathan Z. Dau; David J. Lessley; Kristy B. Arbogast; Xavier Thompson; Jacob E. Resch; Jeff R. Crandall (Annals of Biomedical Engineering, 2020)

Forested Wetland Hydrology in a Large Mississippi River Tributary System - Jacob F. Berkowitz; David R. Johnson; Jaybus J. Price (Wetlands, 2020)
Wetlands in the Mississippi River Valley provide numerous functions supported by prolonged periods of soil saturation or inundation. However, few studies document forested wetland hydropatterns, especially in altered systems. In this study, we evaluated hydrologic drivers of forested wetlands in the Yazoo Basin, a large Mississippi River tributary system exhibiting regional hydrologic alteration. Results from 56 water table monitoring locations indicate that precipitation induced the majority (76%) of wetland saturation events, defined as soil inundation or water tables within ≤30 cm of the surface for ≥14 consecutive days. Flooding triggered 19% of saturation events, and 5% of events occurred in response to precipitation induced high water tables followed by flood inundation. Data suggest that most wetlands examined (87%) would persist in the absence of flooding, and that duration and inundation patterns differed with dominant water source. A multi-year hydropattern analysis highlights the influence of precipitation derived saturation during low evapotranspiration winter periods, spring flood water contributions in some wetlands, and decreasing water tables throughout summer and fall. A discussion of rainfall normality and stream discharge places the dataset in a larger context. Results reflect changes in historic hydropatterns, informing efforts to maximize wetland functions during forested wetland management and restoration.

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Acute cognitive deficits after traumatic brain injury predict Alzheimer’s disease-like degradation of the human default mode network - Andrei Irimia; Alexander S. Maher; Nikhil N. Chaudhari; Nahian F. Chowdhury; Elliot B. Jacobs (GeroScience, 2020)

Soil bacterial community differences along a coastal restoration chronosequence - Dongfeng Yan; Andrew Bissett; Nicholas Gellie; Jacob G. Mills; Andrew J. Lowe; Martin F. Breed (Plant Ecology, 2020)

Environmental stress under climate change reduces plant performance, yet increases allelopathic potential of an invasive shrub - Silvia Medina-Villar; Mercedes Uscola; Mª Esther Pérez-Corona; Douglass F. Jacobs (Biological Invasions, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Multi-Year Viability of a Reef Coral Population Living on Mangrove Roots Suggests an Important Role for Mangroves in the Broader Habitat Mosaic of Corals - Karina Scavo Lord; Kathryn C. Lesneski; Zachary A. Bengtsson; Kirsten M. Kuhn; Joshua Madin; Beatrice Cheung; Roseline Ewa; Jacob F. Taylor; Elizabeth M. Burmester; Joshua Morey; Les Kaufman; John R. Finnerty (Frontiers in Marine Science, 2020)

Soil P Storage Capacity in Agricultural Treatment Wetlands: Can a System Designed for N Reduction Also Retain P? - Christine M. VanZomeren; Jacob F. Berkowitz; A. Maria Lemke; Krista G. Kirkham (Wetlands, 2020)
Increasing interest focuses on utilizing wetlands to reduce nutrient loading to surface waters. The current study examines soil P storage capacity in three treatment wetlands designed to decrease N loading from an agricultural tile drainage system in Illinois. Adjacent farm field and restored floodplain wetland soils were also evaluated. Results demonstrate that wetland soils sequestered P; however, the magnitude of P retention varied significantly across treatment systems and floodplain wetlands related to differences in soil properties. Soil P storage capacity increased in the direction of water flow, but varied across treatment wetlands; soils ranged from P sinks (5.8 ± 1.5 mg P kg −1 ) to potential P sources (−17.2 ± 2.0 mg P kg −1 ). Farm fields displayed the highest water soluble P levels (11.3 ± 1.5 mg P kg −1 ) and represented the largest potential source of P with a mean storage capacity of −48.6 ± 6.8 mg P kg −1 . A phosphorus saturation ratio threshold value of 0.10 differentiated between potential P sources and sinks. Findings suggest wetlands receiving P loadings from tile drainage accumulate soil P over time, but maintaining P removal efficiency in treatment wetlands may require periodic management to decrease soil P concentrations via nutrient removal and/or soil amendments.

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.

Isolation and characterization of microsatellite loci in Astroniumgraveolens (Anacardiaceae) and cross amplification in related species - Karman F. Sanchez-Gomez; E. Jacob Cristóbal-Pérez; Nick Harvey; Mauricio Quesada (Molecular Biology Reports, 2020)

Efficacy of mating disruption compared with chemical insecticides for controlling Tuta absoluta (Lepidoptera: Gelechiidae) in Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Joby Jacob; Omar Al-Saeed (Applied Entomology and Zoology, 2020)

Implications of the movement behaviour of African tigerfish Hydrocynus vittatus for the design of freshwater protected areas - Francois J. Jacobs; Tor F. Næsje; Eva M. Ulvan; Olaf L. F. Weyl; Deon Tiyeho; Clinton J. Hay; Gordon C. O'Brien; Colleen T. Downs (Journal of Fish Biology, 2020)
African tigerfish Hydrocynus vittatus ( n = 35) were tagged with external radio‐transmitters in the Kavango River, Namibia, to determine whether freshwater protected areas could be an effective tool for the management and conservation of this species. They were manually tracked in the core study area of 33 km every c . 12 days from July–October 2016 to May 2017 for between 123 to 246 days. In addition, 14 extended surveys were carried out for up to 680 km to determine the total area use of the tagged individuals. Tigerfish displayed at least two behavioural patterns either having high site fidelity with shorter movements or using larger areas with longer movements. Twenty‐three (66%) of the tigerfish had high site fidelity using an area of less than 33 km of river, whereas 12 tigerfish (34%) undertook long distance movements of up to 397 km upstream and 116 km downstream from their tagging locations. During the long‐distance movements tigerfish crossed the territorial boundaries of Angola, Namibia and Botswana. Of the 35 fish that were monitored, 14 (40%) spent more than 80% of the monitored time in the 33 km study area and 18 (51%) stayed within the study area for at least 50% of the monitored time. These findings suggest that freshwater protected areas may be a useful management tool and we predict that a protected river area of 2–5 km river length could protect 25.9–34.6% of the population for at least 75% of the time whereas protection of 10 km river length could protect at least 50% of tigerfish for at least 75% of the time.

Preparing for a changing future in recreational fisheries: 100 research questions for global consideration emerging from a horizon scan - Peter E. Holder; Amanda L. Jeanson; Robert J. Lennox; Jacob W. Brownscombe; Robert Arlinghaus; Andy J. Danylchuk; Shannon D. Bower; Kieran Hyder; Len M. Hunt; Eli P. Fenichel; Paul A. Venturelli; Eva B. Thorstad; et al. (Reviews in Fish Biology and Fisheries, 2020)

Hospitalizations for infections by age and sex: register-based study of Danish children 1977–2014 - Jacob W. W. Larsen; Anders F. Sørensen; Aksel K. G. Jensen; Anja Poulsen; Lise Gehrt; Christine S. Benn; Signe Sørup (Infectious Diseases, 2020)

Correction to: Alarm call modification by prairie dogs in the presence of juveniles - Grete E. Wilson-Henjum; Jacob R. Job; Megan F. McKenna; Graeme Shannon; George Wittemyer (Journal of Ethology, 2020)
The article Alarm call modification by prairie dogs in the presence of juveniles

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Comparison of the novel dipstick DNA extraction technique with two established techniques for use in biological barcoding - Avrie Martello; Brett Lambert; Clifton Johnston; Jacob Cutler; Christof F. Stumpf (Molecular Biology Reports, 2019)

Inhibitory Control Deficits Associated with Upregulation of CB1R in the HIV-1 Tat Transgenic Mouse Model of Hand - Ian R. Jacobs; Changqing Xu; Douglas J. Hermes; Alexis F. League; Callie Xu; Bhupendra Nath; Wei Jiang; Micah J. Niphakis; Benjamin F. Cravatt; Ken Mackie; Somnath Mukhopadhyay; Aron H. Lichtman; et al. (Journal of Neuroimmune Pharmacology, 2019)

Archaeobotanical investigations at the earliest horse herder site of Botai in Kazakhstan - Giedre Motuzaite Matuzeviciute; E. Lightfoot; X. Liu; J. Jacob; A. K. Outram; V. F. Zaibert; S. Zakharov; M. K. Jones (Archaeological and Anthropological Sciences, 2019)

Oral acute toxicity and impact of neonicotinoids on Apis mellifera L. and Scaptotrigona postica Latreille (Hymenoptera: Apidae) - Cynthia R. O. Jacob; José B. Malaquias; Odimar Z. Zanardi; Carina A. S. Silva; Jessica F. O. Jacob; Pedro T. Yamamoto (Ecotoxicology, 2019)

Late Pleistocene range expansion of North American topminnows accompanied by admixture and introgression - David D. Duvernell; Eric Westhafer; Jacob F. Schaefer (Journal of Biogeography, 2019)
Aim We used genome‐scale sampling to assess the phylogeography of a group of topminnows in the Fundulus notatus species complex. Two of the species have undergone extensive range expansions resulting in broadly overlapping distributions, and sympatry within drainages has provided opportunities for hybridization and introgression. We assessed the timing and pattern of range expansion in the context of late Pleistocene–Holocene drainage events and evaluated the evidence for introgressive hybridization between species. Location Central and southern United States including drainages of the Gulf of Mexico Coastal Plain and portions of the Mississippi River drainage in and around the Central Highlands. Taxon Topminnows, Genus Fundulus , subgenus Zygonectes — Fundulus notatus, Fundulus olivaceus, Fundulus euryzonus . Methods We sampled members of the F. notatus species complex throughout their respective ranges, including numerous drainage systems where species co‐occur. We collected genome‐wide single nucleotide polymorphisms ( SNP s) using the genotype‐by‐sequencing ( GBS ) method and subjected data to population genetic analyses to infer the population histories of both species, including explicit tests for admixture and introgression. The methods employed included STRUCTURE , principal coordinates analysis, TreeMix and approximate Bayesian computation. Results Genetic data are presented for 749 individuals sampled from 14 F. notatus , 20 F. olivaceus and 2 F. euryzonus populations. Members of the species complex differed in phylogeographic structure, with F. notatus exhibiting geographic clusters corresponding to Pleistocene coastal drainages and F. olivaceus comparatively lacking in phylogeographic structure. Evidence for interspecific introgression varied by drainage. Main conclusions Populations of F. notatus and F. olivaceus exhibited contrasting patterns of lineage diversity among coastal drainages, indicating interspecific differences in their Pleistocene southern refugia. Phylogeographic patterns in both species indicated that range expansions into the northern limits of contemporary distributions coincided with and continued subsequent to the Last Glacial Maximum. There was evidence of introgression between species in some, but not all drainages where the species co‐occur, in a pattern that is correlated with previous estimates of hybridization rates.

Improving Hydric Soil Identification in Areas Containing Problematic Red Parent Materials: a Nationwide Collaborative Mapping Approach - Sara C. Mack; Jacob F. Berkowitz; Martin C. Rabenhorst (Wetlands, 2019)

Career Performance Progressions of Junior and Senior Elite Track and Field Athletes - Joshua L. Foss; Jacob A. Sinex; Robert F. Chapman (Journal of Science in Sport and Exercise, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Up-scaling of crop productivity estimations using the AquaCrop model and GIS-based operations - I. Alaya; M. M. Masmoudi; F. Jacob; N. Ben Mechlia (Arabian Journal of Geosciences, 2019)

Quantifying Functional Increases Across a Large-Scale Wetland Restoration Chronosequence - Jacob F. Berkowitz (Wetlands, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

Litter Decomposition in Yellowstone Grasslands: The Roles of Large Herbivores, Litter Quality, and Climate - Jacob F. Penner; Douglas A. Frank (Ecosystems, 2019)

Alarm call modification by prairie dogs in the presence of juveniles - Grete E. Wilson-Henjum; Jacob R. Job; Megan F. McKenna; Graeme Shannon; George Wittemyer (Journal of Ethology, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Use of AquaCrop model for estimating crop evapotranspiration and biomass production in hilly topography - N. Boudhina; M. M Masmoudi; I. Alaya; F. Jacob; N. Ben Mechlia (Arabian Journal of Geosciences, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Restoring forests: regeneration and ecosystem function for the future - Magnus Löf; Palle Madsen; Marek Metslaid; Johanna Witzell; Douglass F. Jacobs (New Forests, 2019)

Different loci associated with root and foliar resistance to sudden death syndrome (Fusarium virguliforme) in soybean - Ruijuan Tan; Paul J. Collins; Jie Wang; Zixiang Wen; John F. Boyse; Randall G. Laurenz; Cuihua Gu; Janette L. Jacobs; Qijian Song; Martin I. Chilvers; Dechun Wang (Theoretical and Applied Genetics, 2019)

Modeling Human Volunteers in Multidirectional, Uni-axial Sled Tests Using a Finite Element Human Body Model - James P. Gaewsky; Derek A. Jones; Xin Ye; Bharath Koya; Kyle P. McNamara; F. Scott Gayzik; Ashley A. Weaver; Jacob B. Putnam; Jeffrey T. Somers; Joel D. Stitzel (Annals of Biomedical Engineering, 2019)

Characterization of mule deerpox virus in Florida white-tailed deer fawns expands the known host and geographic range of this emerging pathogen - Katherine A. Sayler; Kuttichantran Subramaniam; Jessica M. Jacob; Julia C. Loeb; William F. Craft; Lisa L. Farina; Nicole I. Stacy; Nissin Moussatche; Laurie Cook; John A. Lednicky; Samantha M. Wisely; Thomas B. Waltzek (Archives of Virology, 2019)

Are all bony fishes oxygen regulators? Evidence for oxygen regulation in a putative oxygen conformer, the swamp eel Synbranchus marmoratus - Morten Bo Søndergaard Svendsen; Jacob L. Johansen; Peter G. Bushnell; Peter V. Skov; Tommy Norin; Paolo Domenici; John F. Steffensen; Augusto Abe (Journal of Fish Biology, 2019)
This study investigated the oxygen consumption of the putative oxygen conformer marbled swamp eel Synbranchus marmoratus during progressive hypoxia. Earlier studies have not reached an agreement on whether S. marmoratus is a conformer or a regulator. Our results support the view that S. marmoratus is an oxygen regulator, like most bony fishes.

Genotypic variation in phenological plasticity: Reciprocal common gardens reveal adaptive responses to warmer springs but not to fall frost - Hillary F. Cooper; Kevin C. Grady; Jacob A. Cowan; Rebecca J. Best; Gerard J. Allan; Thomas G. Whitham (Global Change Biology, 2019)
Species faced with rapidly shifting environments must be able to move, adapt, or acclimate in order to survive. One mechanism to meet this challenge is phenotypic plasticity: altering phenotype in response to environmental change. Here, we investigated the magnitude, direction, and consequences of changes in two key phenology traits (fall bud set and spring bud flush) in a widespread riparian tree species, Populus fremontii . Using replicated genotypes from 16 populations from throughout the species’ thermal range, and reciprocal common gardens at hot, warm, and cool sites, we identified four major findings: (a) There are significant genetic (G), environmental (E), and GxE components of variation for both traits across three common gardens; (b) The magnitude of phenotypic plasticity is correlated with provenance climate, where trees from hotter, southern populations exhibited up to four times greater plasticity compared to the northern, frost‐adapted populations; (c) Phenological mismatches are correlated with higher mortality as the transfer distances between provenance and garden increase; and (d) The relationship between plasticity and survival depends not only on the magnitude and direction of environmental transfer, but also on the type of environmental stress (i.e., heat or freezing), and how particular traits have evolved in response to that stress. Trees transferred to warmer climates generally showed small to moderate shifts in an adaptive direction, a hopeful result for climate change. Trees experiencing cooler climates exhibited large, non‐adaptive changes, suggesting smaller transfer distances for assisted migration. This study is especially important as it deconstructs trait responses to environmental cues that are rapidly changing (e.g., temperature and spring onset) and those that are fixed (photoperiod), and that vary across the species’ range. Understanding the magnitude and adaptive nature of phenotypic plasticity of multiple traits responding to multiple environmental cues is key to guiding restoration management decisions as climate continues to change.

The Global Naturalized Alien Flora (Glo NAF ) database - Mark van Kleunen; Petr Pyšek; Wayne Dawson; Franz Essl; Holger Kreft; Jan Pergl; Patrick Weigelt; Anke Stein; Stefan Dullinger; Christian König; Bernd Lenzner; Noëlie Maurel; et al. (Ecology, 2019)
This dataset provides the Global Naturalized Alien Flora (Glo NAF ) database, version 1.2. Glo NAF represents a data compendium on the occurrence and identity of naturalized alien vascular plant taxa across geographic regions (e.g. countries, states, provinces, districts, islands) around the globe. The dataset includes 13,939 taxa and covers 1,029 regions (including 381 islands). The dataset is based on 210 data sources. For each taxon‐by‐region combination, we provide information on whether the taxon is considered to be naturalized in the specific region (i.e. has established self‐sustaining populations in the wild). Non‐native taxa are marked as “alien”, when it is not clear whether they are naturalized. To facilitate alignment with other plant databases, we provide for each taxon the name as given in the original data source and the standardized taxon and family names used by The Plant List Version 1.1 ( http://www.theplantlist.org/ ). We provide an ESRI shapefile including polygons for each region and information on whether it is an island or a mainland region, the country and the Taxonomic Databases Working Group ( TDWG ) regions it is part of ( TDWG levels 1–4). We also provide several variables that can be used to filter the data according to quality and completeness of alien taxon lists, which vary among the combinations of regions and data sources. A previous version of the Glo NAF dataset (version 1.1) has already been used in several studies on, for example, historical spatial flows of taxa between continents and geographical patterns and determinants of naturalization across different taxonomic groups. We intend the updated and expanded Glo NAF version presented here to be a global resource useful for studying plant invasions and changes in biodiversity from regional to global scales. We release these data into the public domain under a Creative Commons Zero license waiver ( https://creativecommons.org/share-your-work/public-domain/cc0/ ). When you use the data in your publication, we request that you cite this data paper. If Glo NAF is a major part of the data analyzed in your study, you should consider inviting the Glo NAF core team (see Metadata S1: Originators in the Overall project description) as collaborators. If you plan to use the Glo NAF dataset, we encourage you to contact the Glo NAF core team to check whether there have been recent updates of the dataset, and whether similar analyses are already ongoing.

Effects of landscape plant species and concentration of sewage sludge compost on plant growth, nutrient uptake, and heavy metal removal - Shuangshuang Chu; Douglass F. Jacobs; Dandan Liao; Liyin L. Liang; Daoming Wu; Peijiang Chen; Can Lai; Fengdi Zhong; Shucai Zeng (Environmental Science and Pollution Research, 2018)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Forest regeneration in changing environments - Robert G. Wagner; Carlos A. Gonzalez-Benecke; Andrew S. Nelson; Douglass F. Jacobs (New Forests, 2018)

Conversion of conifer plantations to native hardwoods: influences of overstory and fertilization on artificial regeneration - Jenny Lesko; Douglass F. Jacobs (New Forests, 2018)

Too hot to handle? Using movement to alleviate effects of elevated temperatures in a benthic elasmobranch, Hemiscyllium ocellatum - Connor R. Gervais; Tiffany J. Nay; Gillian Renshaw; Jacob L. Johansen; John F. Steffensen; Jodie L. Rummer (Marine Biology, 2018)

Chromogenic media for the detection of Salmonella enterica serovar Paratyphi A in human stool samples: evaluation in a reference setting - L. M. F. Kuijpers; A. S. Post; J. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Forecasting effects of tree species reintroduction strategies on carbon stocks in a future without historical analog - Eric J. Gustafson; Brian R. Sturtevant; Arjan M. G. de Bruijn; Nathanael Lichti; Douglass F. Jacobs; Daniel M. Kashian; Brian R. Miranda; Philip A. Townsend (Global Change Biology, 2018)
American chestnut ( Castanea dentata ) was once an important component forests in the central Appalachians (USA), but it was functionally extirpated nearly a century ago. Attempts are underway to reintroduce blight‐resistant chestnut to its former range, but it is uncertain how current forest composition, climate, and atmospheric changes and disturbance regimes will interact to determine future forest dynamics and ecosystem services. The combination of novel environmental conditions (e.g. climate change), a reintroduced tree species and new disturbance regimes (e.g. exotic insect pests, fire suppression) have no analog in the past that can be used to parameterize phenomenological models. We therefore used a mechanistic approach within the LANDIS‐II forest landscape model that relies on physiological first principles to project forest dynamics as the outcome of competition of tree cohorts for light and water as a function of temperature, precipitation, CO 2 concentration, and life history traits. We conducted a factorial landscape simulation experiment to evaluate specific hypotheses about future forest dynamics in two study sites in the center of the former range of chestnut. Our results supported the hypotheses that climate change would favor chestnut because of its optimal temperature range and relative drought resistance, and that chestnut would be less competitive in the more mesic Appalachian Plateau province because competitors will be less stressed. The hypothesis that chestnut will increase carbon stocks was supported, although the increase was modest. Our results confirm that aggressive restoration is needed regardless of climate and soils, and that increased aggressiveness of chestnut restoration increased biomass accumulation. The hypothesis that chestnut restoration will increase both compositional and structural richness was not supported because chestnut displaced some species and age cohorts. Although chestnut restoration did not markedly enhance carbon stocks, our findings provide hope that this formerly important species can be successfully reintroduced and associated ecosystem services recovered.

Reductions in net photosynthesis and stomatal conductance vary with time since leaf detachment in three deciduous angiosperms - Martin-Michel Gauthier; Douglass F. Jacobs (Trees, 2018)

Plantation performance of chestnut hybrids and progenitors on reclaimed Appalachian surface mines - Jeff G. Skousen; Kara Dallaire; Steffany Scagline-Mellor; Alexis Monteleone; Lindsay Wilson-Kokes; Jessica Joyce; Calene Thomas; Travis Keene; Curtis DeLong; Thomas Cook; Douglass F. Jacobs (New Forests, 2018)

Chemical regulation of body feather microbiota in a wild bird - Staffan Jacob; Louis Sallé; Lucie Zinger; Alexis S. Chaine; Christine Ducamp; Léa Boutault; Andrew F. Russell; Philipp Heeb (Molecular Ecology, 2018)
The microbiota has a broad range of impacts on host physiology and behaviour, pointing out the need to improve our comprehension of the drivers of host–microbiota composition. Of particular interest is whether the microbiota is acquired passively, or whether and to what extent hosts themselves shape the acquisition and maintenance of their microbiota. In birds, the uropygial gland produces oily secretions used to coat feathers that have been suggested to act as an antimicrobial defence mechanism regulating body feather microbiota. However, our comprehension of this process is still limited. In this study, we for the first time coupled high‐throughput sequencing of the microbiota of both body feathers and the direct environment (i.e., the nest) in great tits with chemical analyses of the composition of uropygial gland secretions to examine whether host chemicals have either specific effects on some bacteria or nonspecific broad‐spectrum effects on the body feather microbiota. Using a network approach investigating the patterns of co‐occurrence or co‐exclusions between chemicals and bacteria within the body feather microbiota, we found no evidence for specific promicrobial or antimicrobial effects of uropygial gland chemicals. However, we found that one group of chemicals was negatively correlated to bacterial richness on body feathers, and a higher production of these chemicals was associated with a poorer body feather bacterial richness compared to the nest microbiota. Our study provides evidence that chemicals produced by the host might function as a nonspecific broad‐spectrum antimicrobial defence mechanism limiting colonization and/or maintenance of bacteria on body feathers, providing new insight about the drivers of the host's microbiota composition in wild organisms.

Simulated predation of Quercus variabilis acorns impairs nutrient remobilization and seedling performance irrespective of soil fertility - Wenhui Shi; Pedro Villar-Salvador; Douglass F. Jacobs; Guolei Li; Xiaoxu Jiang (Plant and Soil, 2018)

Rapid and efficient CRISPR/Cas9 gene editing in Citrus using the YAO promoter - Fei Zhang; Chantal LeBlanc; Vivian F. Irish; Yannick Jacob (Plant Cell Reports, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Soil pH, organic matter, and nutrient content change with the continuous cropping of Cunninghamia lanceolata plantations in South China - Yuanchun Yu; Jingyu Yang; Shucai Zeng; Daoming Wu; Douglass F. Jacobs; Joshua L. Sloan (Journal of Soils and Sediments, 2017)

Linking the Abundance of Estuarine Fish and Crustaceans in Nearshore Waters to Shoreline Hardening and Land Cover - Matthew S. Kornis; Denise Breitburg; Richard Balouskus; Donna M. Bilkovic; Lori A. Davias; Steve Giordano; Keira Heggie; Anson H. Hines; John M. Jacobs; Thomas E. Jordan; Ryan S. King; Christopher J. Patrick; et al. (Estuaries and Coasts, 2017)

Low-cost water-lifting from groundwater sources: a comparison of the EMAS Pump with the Rope Pump - Michael F. MacCarthy; Jacob D. Carpenter; James R. Mihelcic (Hydrogeology Journal, 2017)

Gene expression profiles predictive of cold-induced sweetening in potato - Jonathan Neilson; M. Lagüe; S. Thomson; F. Aurousseau; A. M. Murphy; B. Bizimungu; V. Deveaux; Y. Bègue; J. M. E. Jacobs; H. H. Tai (Functional & Integrative Genomics, 2017)

Characterisation of Staphylococcus aureus isolates from bloodstream infections, Democratic Republic of the Congo - S. Vandendriessche; H. De Boeck; A. Deplano; M.-F. Phoba; O. Lunguya; D. Falay; N. Dauly; J. Verhaegen; O. Denis; J. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Colonization by nitrogen-fixing Frankia bacteria causes short-term increases in herbivore susceptibility in red alder (Alnus rubra) seedlings - Daniel J. Ballhorn; Jacob D. Elias; M. A. Balkan; Rachel F. Fordyce; Peter G. Kennedy (Oecologia, 2017)

Cognitive reserve moderates the relationship between neuropsychological performance and white matter fiber bundle length in healthy older adults - Laurie M. Baker; David H. Laidlaw; Ryan Cabeen; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; David F. Tate; Jodi M. Heaps-Woodruff; Matthew R. Brier; Jacob Bolzenius; Lauren E. Salminen; Elizabeth M. Lane; et al. (Brain Imaging and Behavior, 2017)

Revegetation rewilds the soil bacterial microbiome of an old field - Nicholas J. C. Gellie; Jacob G. Mills; Martin F. Breed; Andrew J. Lowe (Molecular Ecology, 2017)
Ecological restoration is a globally important and well‐financed management intervention used to combat biodiversity declines and land degradation. Most restoration aims to increase biodiversity towards a reference state, but there are concerns that intended outcomes are not reached due to unsuccessful interventions and land‐use legacy issues. Monitoring biodiversity recovery is essential to measure success; however, most projects remain insufficiently monitored. Current field‐based methods are hard to standardize and are limited in their ability to assess important components of ecosystems, such as bacteria. High‐throughput amplicon sequencing of environmental DNA (metabarcoding of eDNA ) has been proposed as a cost‐effective, scalable and uniform ecological monitoring solution, but its application in restoration remains largely untested. Here we show that metabarcoding of soil eDNA is effective at demonstrating the return of the native bacterial community in an old field following native plant revegetation. Bacterial composition shifted significantly after 8 years of revegetation, where younger sites were more similar to cleared sites and older sites were more similar to remnant stands. Revegetation of the native plant community strongly impacted on the belowground bacterial community, despite the revegetated sites having a long and dramatically altered land‐use history (i.e. >100 years grazing). We demonstrate that metabarcoding of eDNA provides an effective way of monitoring changes in bacterial communities that would otherwise go unchecked with conventional monitoring of restoration projects. With further development, awareness of microbial diversity in restoration has significant scope for improving the efficacy of restoration interventions more broadly.

Banking on the future: progress, challenges and opportunities for the genetic conservation of forest trees - Kevin M. Potter; Robert M. Jetton; Andrew Bower; Douglass F. Jacobs; Gary Man; Valerie D. Hipkins; Murphy Westwood (New Forests, 2017)

Effect of Differential Light Quality on Morphology, Photosynthesis, and Antioxidant Enzyme Activity in Camptotheca acuminata Seedlings - Weiwu Yu; Yang Liu; Lili Song; Douglass F. Jacobs; Xuhua Du; Yeqing Ying; Qingsong Shao; Jiasheng Wu (Journal of Plant Growth Regulation, 2017)

Hepatocyte spheroids as a competent in vitro system for drug biotransformation studies: nevirapine as a bioactivation case study - Pedro F. Pinheiro; Sofia A. Pereira; Shrika G. Harjivan; Inês L. Martins; Aline T. Marinho; Madalena Cipriano; Cristina C. Jacob; Nuno G. Oliveira; Matilde F. Castro; M. Matilde Marques; Alexandra M. M. Antunes; Joana P. Miranda (Archives of Toxicology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Adapt, move or die – how will tropical coral reef fishes cope with ocean warming? - Adam Habary; Jacob L. Johansen; Tiffany J. Nay; John F. Steffensen; Jodie L. Rummer (Global Change Biology, 2017)
Previous studies hailed thermal tolerance and the capacity for organisms to acclimate and adapt as the primary pathways for species survival under climate change. Here we challenge this theory. Over the past decade, more than 365 tropical stenothermal fish species have been documented moving poleward, away from ocean warming hotspots where temperatures 2–3 °C above long‐term annual means can compromise critical physiological processes. We examined the capacity of a model species – a thermally sensitive coral reef fish, Chromis viridis (Pomacentridae) – to use preference behaviour to regulate its body temperature. Movement could potentially circumvent the physiological stress response associated with elevated temperatures and may be a strategy relied upon before genetic adaptation can be effectuated. Individuals were maintained at one of six temperatures (23, 25, 27, 29, 31 and 33 °C) for at least 6 weeks. We compared the relative importance of acclimation temperature to changes in upper critical thermal limits, aerobic metabolic scope and thermal preference. While acclimation temperature positively affected the upper critical thermal limit, neither aerobic metabolic scope nor thermal preference exhibited such plasticity. Importantly, when given the choice to stay in a habitat reflecting their acclimation temperatures or relocate, fish acclimated to end‐of‐century predicted temperatures (i.e. 31 or 33 °C) preferentially sought out cooler temperatures, those equivalent to long‐term summer averages in their natural habitats (~29 °C). This was also the temperature providing the greatest aerobic metabolic scope and body condition across all treatments. Consequently, acclimation can confer plasticity in some performance traits, but may be an unreliable indicator of the ultimate survival and distribution of mobile stenothermal species under global warming. Conversely, thermal preference can arise long before, and remain long after, the harmful effects of elevated ocean temperatures take hold and may be the primary driver of the escalating poleward migration of species.

Central Nervous System and Vertebrae Development in Horses: a Chronological Study with Differential Temporal Expression of Nestin and GFAP - Nathia N. Rigoglio; Rodrigo S. N. Barreto; Phelipe O. Favaron; Júlio C. F. Jacob; Lawrence C. Smith; Melba O. Gastal; Eduardo L. Gastal; Maria Angélica Miglino (Journal of Molecular Neuroscience, 2017)

Daily precipitation statistics in a EURO-CORDEX RCM ensemble: added value of raw and bias-corrected high-resolution simulations - A. Casanueva; S. Kotlarski; S. Herrera; J. Fernández; J. M. Gutiérrez; F. Boberg; A. Colette; O. B. Christensen; K. Goergen; D. Jacob; K. Keuler; G. Nikulin; et al. (Climate Dynamics, 2016)

A mouse model of the 15q13.3 microdeletion syndrome shows prefrontal neurophysiological dysfunctions and attentional impairment - Simon R. O. Nilsson; Pau Celada; Kim Fejgin; Jonas Thelin; Jacob Nielsen; Noemí Santana; Christopher J. Heath; Peter H. Larsen; Vibeke Nielsen; Brianne A. Kent; Lisa M. Saksida; Tine B. Stensbøl; et al. (Psychopharmacology, 2016)

The role of competition – colonization tradeoffs and spatial heterogeneity in promoting trematode coexistence - Erin A. Mordecai; Alejandra G. Jaramillo; Jacob E. Ashford; Ryan F. Hechinger; Kevin D. Lafferty (Ecology, 2016)
Competition – colonization tradeoffs occur in many systems, and theory predicts that they can strongly promote species coexistence. However, there is little empirical evidence that observed competition‐ colonization tradeoffs are strong enough to maintain diversity in natural systems. This is due in part to a mismatch between theoretical assumptions and biological reality in some systems. We tested whether a competition – colonization tradeoff explains how a diverse trematode guild coexists in California horn snail populations, a system that meets the requisite criteria for the tradeoff to promote coexistence. A field experiment showed that subordinate trematode species tended to have higher colonization rates than dominant species. This tradeoff promoted coexistence in parameterized models but did not fully explain trematode diversity and abundance, suggesting a role of additional diversity maintenance mechanisms. Spatial heterogeneity is an alternative way to promote coexistence if it isolates competing species. We used scale transition theory to expand the competition – colonization tradeoff model to include spatial variation. The parameterized model showed that spatial variation in trematode prevalence did not isolate most species sufficiently to explain the overall high diversity, but could benefit some rare species. Together, the results suggest that several mechanisms combine to maintain diversity, even when a competition – colonization tradeoff occurs.

Ecological influences on the local movement dynamics of the blackspotted topminnow, Fundulus olivaceus - Scott R. Clark; Jacob F. Schaefer (Behavioral Ecology and Sociobiology, 2016)

Ancient river systems and phylogeographical structure in the spring salamander, Gyrinophilus porphyriticus - Shawn R. Kuchta; Michael Haughey; Addison H. Wynn; Jeremy F. Jacobs; Richard Highton (Journal of Biogeography, 2016)
Aim The river drainages of the Appalachian Mountains have experienced a dynamic history as glacial cycles, stream capture and other geological processes have led to the fragmentation and fusion of formerly isolated palaeodrainages. Some ancient rivers have gone extinct, including portions of the great Teays River. Here we investigate the contribution of contemporary and historical drainages to patterns of phylogeographical structure in the spring salamander complex, Gyrinophilus porphyriticus . Location Eastern North America, USA . Methods Sampling spanned the range of the G. porphyriticus complex, and included representative samples of the cave species of Gyrinophilus as well. Molecular sequence data included the mitochondrial DNA locus cytochrome b and the nuclear locus recombination‐activating gene 1 ( RAG ‐1). Time‐calibrated phylogenies were inferred, and Bayes‐ LAGRANGE was used to reconstruct ancestral distributions. Contemporary and historical river influences on patterns of genetic diversity were tested using distance‐based redundancy analysis (db‐ RDA ). Results The G. porphyriticus complex originated prior to the Pleistocene glacial cycles, and historical river systems explained more genetic variation than did contemporary drainages or geographical distance. Patterns of genetic variation suggest that extinct or remodelled palaeodrainages, including the Teays River, played an important role in structuring contemporary patterns of genetic variation. Main conclusions The hydrogeological history of eastern North American drainage basins has been instrumental in structuring patterns of regional biodiversity in freshwater species. Here we show that hydrological remodelling has also left its genetic signature in the semi‐aquatic spring salamander complex, G. porphyriticus . Historical drainages accounted for the largest fraction of phylogeographical structure, more so than did contemporary drainages or geographical distance, with spatial and temporal patterns of variation associated with the extinct Teays River.

Football training in men with prostate cancer undergoing androgen deprivation therapy: activity profile and short-term skeletal and postural balance adaptations - Jacob Uth; Therese Hornstrup; Jesper F. Christensen; Karl B. Christensen; Niklas R. Jørgensen; Eva W. Helge; Jakob F. Schmidt; Klaus Brasso; Jørn W. Helge; Markus D. Jakobsen; Lars L. Andersen; Mikael Rørth; et al. (European Journal of Applied Physiology, 2016)

Precipitation in the EURO-CORDEX $$0.11^{° }$$ 0 . 11 ∘ and $$0.44^{° }$$ 0 . 44 ∘ simulations: high resolution, high benefits? - A. F. Prein; A. Gobiet; H. Truhetz; K. Keuler; K. Goergen; C. Teichmann; C. Fox Maule; E. van Meijgaard; M. Déqué; G. Nikulin; R. Vautard; A. Colette; et al. (Climate Dynamics, 2016)

Modeling Population-Level Consequences of Polychlorinated Biphenyl Exposure in East Greenland Polar Bears - Viola Pavlova; Volker Grimm; Rune Dietz; Christian Sonne; Katrin Vorkamp; Frank F. Rigét; Robert J. Letcher; Kim Gustavson; Jean-Pierre Desforges; Jacob Nabe-Nielsen (Archives of Environmental Contamination and Toxicology, 2016)

Behavioural thermoregulation in a temperature-sensitive coral reef fish, the five-lined cardinalfish (Cheilodipterus quinquelineatus) - Tiffany J. Nay; Jacob L. Johansen; Adam Habary; John F. Steffensen; Jodie L. Rummer (Coral Reefs, 2015)

The effect of personal medical history and family history of cancer on the uptake of risk-reducing salpingo-oophorectomy - Jessica E. van der Aa; Jacob P. Hoogendam; Els S. F. Butter; Margreet G. E. M. Ausems; René H. M. Verheijen; Ronald P. Zweemer (Familial Cancer, 2015)

Restoring forests: What constitutes success in the twenty-first century? - Douglass F. Jacobs; Juan A. Oliet; James Aronson; Andreas Bolte; James M. Bullock; Pablo J. Donoso; Simon M. Landhäusser; Palle Madsen; Shaolin Peng; José M. Rey-Benayas; John C. Weber (New Forests, 2015)

Forest restoration following surface mining disturbance: challenges and solutions - S. Ellen Macdonald; Simon M. Landhäusser; Jeff Skousen; Jennifer Franklin; Jan Frouz; Sarah Hall; Douglass F. Jacobs; Sylvie Quideau (New Forests, 2015)

Can the use of large, alternative nursery containers aid in field establishment of Juglans regia and Quercus robur seedlings? - Barbara Mariotti; Alberto Maltoni; Pier Mario Chiarabaglio; Achille Giorcelli; Douglass F. Jacobs; Roberto Tognetti; Andrea Tani (New Forests, 2015)

The role of stored carbohydrates and nitrogen in the growth and stress tolerance of planted forest trees - Pedro Villar-Salvador; Mercedes Uscola; Douglass F. Jacobs (New Forests, 2015)

An exponential fertilization dose–response model to promote restoration of the Mediterranean oak Quercus ilex - Mercedes Uscola; K. Francis Salifu; Juan A. Oliet; Douglass F. Jacobs (New Forests, 2015)

Swimming energetics and thermal ecology of adult bonefish (Albula vulpes): a combined laboratory and field study in Eleuthera, The Bahamas - Liane B. Nowell; Jacob W. Brownscombe; Lee F. G. Gutowsky; Karen J. Murchie; Cory D. Suski; Andy J. Danylchuk; Aaron Shultz; Steven J. Cooke (Environmental Biology of Fishes, 2015)

Recovery of African wild dogs suppresses prey but does not trigger a trophic cascade - Adam T. Ford; Jacob R. Goheen; David J. Augustine; Margaret F. Kinnaird; Timothy G. O'Brien; Todd M. Palmer; Robert M. Pringle; Rosie Woodroffe (Ecology, 2015)
Increasingly, the restoration of large carnivores is proposed as a means through which to restore community structure and ecosystem function via trophic cascades. After a decades‐long absence, African wild dogs ( Lycaon pictus ) recolonized the Laikipia Plateau in central Kenya, which we hypothesized would trigger a trophic cascade via suppression of their primary prey (dik‐dik, Madoqua guentheri ) and the subsequent relaxation of browsing pressure on trees. We tested the trophic‐cascade hypothesis using (1) a 14‐year time series of wild dog abundance; (2) surveys of dik‐dik population densities conducted before and after wild dog recovery; and (3) two separate, replicated, herbivore‐exclusion experiments initiated before and after wild dog recovery. The dik‐dik population declined by 33% following wild dog recovery, which is best explained by wild dog predation. Dik‐dik browsing suppressed tree abundance, but the strength of suppression did not differ between before and after wild dog recovery. Despite strong, top‐down limitation between adjacent trophic levels (carnivore–herbivore and herbivore–plant), a trophic cascade did not occur, possibly because of a time lag in indirect effects, variation in rainfall, and foraging by herbivores other than dik‐dik. Our ability to reject the trophic‐cascade hypothesis required two important approaches: (1) temporally replicated herbivore exclusions, separately established before and after wild dog recovery; and (2) evaluating multiple drivers of variation in the abundance of dik‐dik and trees. While the restoration of large carnivores is often a conservation priority, our results suggest that indirect effects are mediated by ecological context, and that trophic cascades are not a foregone conclusion of such recoveries.

Genetics of skin color variation in Europeans: genome-wide association studies with functional follow-up - Fan Liu; Mijke Visser; David L. Duffy; Pirro G. Hysi; Leonie C. Jacobs; Oscar Lao; Kaiyin Zhong; Susan Walsh; Lakshmi Chaitanya; Andreas Wollstein; Gu Zhu; Grant W. Montgomery; et al. (Human Genetics, 2015)

Tree shelters affect shoot and root system growth and structure in Quercus robur during regeneration establishment - Barbara Mariotti; Alberto Maltoni; Douglass F. Jacobs; Andrea Tani (European Journal of Forest Research, 2015)

The Contribution of Agriculture, Forestry and other Land Use activities to Global Warming, 1990–2012 - Francesco N. Tubiello; Mirella Salvatore; Alessandro F. Ferrara; Jo House; Sandro Federici; Simone Rossi; Riccardo Biancalani; Rocio D. Condor Golec; Heather Jacobs; Alessandro Flammini; Paolo Prosperi; Paola Cardenas‐Galindo; et al. (Global Change Biology, 2015)
We refine the information available through the IPCC AR 5 with regard to recent trends in global GHG emissions from agriculture, forestry and other land uses ( AFOLU ), including global emission updates to 2012. Using all three available AFOLU datasets employed for analysis in the IPCC AR 5, rather than just one as done in the IPCC AR 5 WGIII Summary for Policy Makers, our analyses point to a down‐revision of global AFOLU shares of total anthropogenic emissions, while providing important additional information on subsectoral trends. Our findings confirm that the share of AFOLU emissions to the anthropogenic total declined over time. They indicate a decadal average of 28.7 ± 1.5% in the 1990s and 23.6 ± 2.1% in the 2000s and an annual value of 21.2 ± 1.5% in 2010. The IPCC AR 5 had indicated a 24% share in 2010. In contrast to previous decades, when emissions from land use (land use, land use change and forestry, including deforestation) were significantly larger than those from agriculture (crop and livestock production), in 2010 agriculture was the larger component, contributing 11.2 ± 0.4% of total GHG emissions, compared to 10.0 ± 1.2% of the land use sector. Deforestation was responsible for only 8% of total anthropogenic emissions in 2010, compared to 12% in the 1990s. Since 2010, the last year assessed by the IPCC AR 5, new FAO estimates indicate that land use emissions have remained stable, at about 4.8 Gt CO 2 eq yr −1 in 2012. Emissions minus removals have also remained stable, at 3.2 Gt CO 2 eq yr −1 in 2012. By contrast, agriculture emissions have continued to grow, at roughly 1% annually, and remained larger than the land use sector, reaching 5.4 Gt CO 2 eq yr −1 in 2012. These results are useful to further inform the current climate policy debate on land use, suggesting that more efforts and resources should be directed to further explore options for mitigation in agriculture, much in line with the large efforts devoted to REDD+ in the past decade.

In Vitro Susceptibility of Brazilian Pythium insidiosum Isolates to Essential Oils of Some Lamiaceae Family Species - A. O. S. Fonseca; D. I. B. Pereira; R. G. Jacob; F. S. Maia Filho; D. H. Oliveira; B. P. Maroneze; J. S. S. Valente; L. G. Osório; S. A. Botton; M. C. A. Meireles (Mycopathologia, 2015)

Social stress and escalated drug self-administration in mice I. Alcohol and corticosterone - Kevin J. Norman; Jacob A. Seiden; Jacob A. Klickstein; Xiao Han; Lara S. Hwa; Joseph F. DeBold; Klaus A. Miczek (Psychopharmacology, 2015)

Humans can integrate feedback of discrete events in their sensorimotor control of a robotic hand - Christian Cipriani; Jacob L. Segil; Francesco Clemente; Richard F. ff. Weir; Benoni Edin (Experimental Brain Research, 2014)

Terpenoid composition and origin of amber from the Cape York Peninsula, Australia - O. O. Sonibare; O. B. Agbaje; D. E. Jacob; J. Faithfull; T. Hoffmann; S. F. Foley (Australian Journal of Earth Sciences, 2014)

Assessing Potato Psyllid Haplotypes in Potato Crops in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Joseph E. Munyaneza; Alexzandra F. Murphy; Silvia I. Rondon; Brandon Thompson; Alexander V. Karasev; Erik J. Wenninger; Nora Olsen; James M. Crosslin (American Journal of Potato Research, 2014)

Novel molecular determinants of viral susceptibility and resistance in the lipidome of E miliania huxleyi - James M. Fulton; Helen F. Fredricks; Kay D. Bidle; Assaf Vardi; B. Jacob Kendrick; Giacomo R. DiTullio; Benjamin A. S. Van Mooy (Environmental Microbiology, 2014)
Summary Viruses play a key role in controlling the population dynamics of algae, including E miliania huxleyi , a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. E miliania huxleyi viruses ( EhVs ) routinely infect and terminate E . huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids ( GSLs ) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusion between the virus and host, and we hypothesized that specific polar lipids may facilitate virus attachment. We identified three novel intact polar lipids in E . huxleyi strain CCMP 374 and EhV 86, including a GSL with a monosaccharide sialic acid headgroup ( sGSL ); for all 11 E . huxleyi strains we tested, there was a direct relationship between sGSL content and sensitivity to infection by EhV 1, EhV 86 and EhV 163. In mesocosms, the E . huxleyi population with greatest initial sGSL content had the highest rate of virus‐induced mortality. We propose potential physiological roles for sGSL that would be beneficial for growth but leave cells susceptible to infection, thus furthering the discussion of R ed Q ueen‐based co‐evolution and the cost(s) of sensitivity and resistance in the dynamic E . huxleyi ‐ EhV system.

Nitrogen form and concentration interact to affect the performance of two ecologically distinct Mediterranean forest trees - Mercedes Uscola; Juan A. Oliet; Pedro Villar-Salvador; Eugenio Díaz-Pinés; Douglass F. Jacobs (European Journal of Forest Research, 2014)

Investigation of Biogeochemical Functional Proxies in Headwater Streams Across a Range of Channel and Catchment Alterations - Jacob F. Berkowitz; Elizabeth A. Summers; Chris V. Noble; John R. White; Ronald D. DeLaune (Environmental Management, 2014)

The fear-factor stress test: an ethical, non-invasive laboratory method that produces consistent and sustained cortisol responding in men and women - Christopher du Plooy; Kevin G. F. Thomas; Michelle Henry; Robyn Human; W. Jake Jacobs (Metabolic Brain Disease, 2014)

Variation in contact zone dynamics between two species of topminnows, Fundulus notatus and F. olivaceus, across isolated drainage systems - David D. Duvernell; Jacob F. Schaefer (Evolutionary Ecology, 2014)

Epidemic increase in Salmonella bloodstream infection in children, Bwamanda, the Democratic Republic of Congo - M.-F. Phoba; H. Boeck; B. B. Ifeka; J. Dawili; O. Lunguya; R. Vanhoof; J.-J. Muyembe; C. Geet; S. Bertrand; J. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Nitrogen fertilization of black walnut (Juglans nigra L.) during plantation establishment. Physiology of production - Rosa C. Goodman; Juan A. Oliet; Joshua L. Sloan; Douglass F. Jacobs (European Journal of Forest Research, 2014)

First observation of African tigerfish Hydrocynus vittatus predating on barn swallows Hirundo rustica in flight - G. C. O'Brien; F. Jacobs; S. W. Evans; N. J. Smit (Journal of Fish Biology, 2014)
A population of African tigerfish Hydrocynus vittatus from the Schroda Dam, actively prey on barn swallows Hirundo rustica in flight. This behaviour was discovered during a radio telemetry study and documented using a motion picture video camera. These results show that an avivorous diet is a part of the feeding biology of H. vittatus , and may occur in other populations.

Simulation of rainfall anomalies leading to the 2005 drought in Amazonia using the CLARIS LPB regional climate models - J. Marengo; S. Chou; C. Mourao; S. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; N. Pessacg; A. R. C. Remedio; A. F. Carril; I. F Cavalcanti; et al. (Climate Dynamics, 2013)

Extracolonic cancer risk in patients with serrated polyposis syndrome and their first-degree relatives - Yark Hazewinkel; Johannes B. Reitsma; Fokko M. Nagengast; Hans F. Vasen; Theo A. M. van Os; Monique E. van Leerdam; Jan-Jacob Koornstra; Evelien Dekker (Familial Cancer, 2013)

Haplotypes of the Potato Psyllid, Bactericera cockerelli, on the Wild Host Plant, Solanum dulcamara, in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Erik Echegaray; Alexzandra F. Murphy; Silvia I. Rondon; Joseph E. Munyaneza; James M. Crosslin (American Journal of Potato Research, 2013)

Ungulate herbivory of boreal and temperate forest regeneration in relation to seedling mineral nutrition and secondary metabolites - Owen T. Burney; Douglass F. Jacobs (New Forests, 2013)

Nutrient dynamics of planted forests - Diane L. Haase; Douglass F. Jacobs (New Forests, 2013)

Nutrient loading of forest tree seedlings to promote stress resistance and field performance: a Mediterranean perspective - Juan A. Oliet; Jaime Puértolas; Rosa Planelles; Douglass F. Jacobs (New Forests, 2013)

Fertilization at planting influences seedling growth and vegetative competition on a post-mining boreal reclamation site - Joshua L. Sloan; Douglass F. Jacobs (New Forests, 2013)

Split fertilizer application affects growth, biomass allocation, and fertilizer uptake efficiency of hybrid Eucalyptus - Shucai Zeng; Douglass F. Jacobs; Joshua L. Sloan; Li Xue; Yin Li; Shuangshuang Chu (New Forests, 2013)

Replication and fine mapping of asthma-associated loci in individuals of African ancestry - David B. Kantor; Cameron D. Palmer; Taylor R. Young; Yan Meng; Zofia K. Gajdos; Helen Lyon; Alkes L. Price; Samuela Pollack; Stephanie J. London; Laura R. Loehr; Lewis J. Smith; Rajesh Kumar; et al. (Human Genetics, 2013)

A Cost-Effective Solution for the Reliable Determination of Cell Numbers of Microorganisms in Liquid Culture - Jacob J. Lamb; Julian J. Eaton-Rye; Martin F. Hohmann-Marriott (Current Microbiology, 2013)

Millwood honeylocust trees: seedpod nutritive value and yield characteristics - Jacob W. Johnson; John H. Fike; Wonae B. Fike; James A. Burger; James R. McKenna; John F. Munsell; Steven C. Hodges (Agroforestry Systems, 2013)

Opioid Receptor Polymorphism A118G Associated with Clinical Severity in a Drug Overdose Population - A. F. Manini; M. M. Jacobs; D. Vlahov; Y. L. Hurd (Journal of Medical Toxicology, 2013)

Prediction of planted seedling survival of five Mediterranean species based on initial seedling morphology - Marianthi Tsakaldimi; Petros Ganatsas; Douglass F. Jacobs (New Forests, 2013)

Optimizing line intercept sampling and estimation for feral swine damage levels in ecologically sensitive wetland plant communities - Jacob F. Thomas; Richard M. Engeman; Eric A. Tillman; Justin W. Fischer; Steve L. Orzell; Deborah H. Glueck; Rodney K. Felix; Michael L. Avery (Environmental Science and Pollution Research, 2013)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Erratum to: Future projections of the surface heat and water budgets of the Mediterranean Sea in an ensemble of coupled atmosphere–ocean regional climate models - C. Dubois; S. Somot; S. Calmanti; A. Carillo; M. Déqué; A. Dell’Aquila; A. Elizalde; S. Gualdi; D. Jacob; B. L’Hévéder; L. Li; P. Oddo; et al. (Climate Dynamics, 2012)

An LED-based fluorometer for chlorophyll quantification in the laboratory and in the field - Jacob J. Lamb; Julian J. Eaton-Rye; Martin F. Hohmann-Marriott (Photosynthesis Research, 2012)

Solid shape discrimination from vision and haptics: natural objects (Capsicum annuum) and Gibson’s “feelies” - J. Farley Norman; Flip Phillips; Jessica S. Holmin; Hideko F. Norman; Amanda M. Beers; Alexandria M. Boswell; Jacob R. Cheeseman; Angela G. Stethen; Cecilia Ronning (Experimental Brain Research, 2012)

Future projections of the surface heat and water budgets of the Mediterranean Sea in an ensemble of coupled atmosphere–ocean regional climate models - C. Dubois; S. Somot; S. Calmanti; A. Carillo; M. Déqué; A. Dell’Aquilla; A. Elizalde; S. Gualdi; D. Jacob; B. L’Hévéder; L. Li; P. Oddo; et al. (Climate Dynamics, 2012)

An Integrated DSS for Groundwater Management Based on Remote Sensing. The Case of a Semi-arid Aquifer in Morocco - Michel Le Page; B. Berjamy; Y. Fakir; F. Bourgin; L. Jarlan; A. Abourida; M. Benrhanem; G. Jacob; M. Huber; F. Sghrer; V. Simonneaux; G. Chehbouni (Water Resources Management, 2012)

Restoring forests: advances in techniques and theory - Juan A. Oliet; Douglass F. Jacobs (New Forests, 2012)

Influence of herbaceous ground cover on forest restoration of eastern US coal surface mines - Jennifer A. Franklin; Carl E. Zipper; James A. Burger; Jeffrey G. Skousen; Douglass F. Jacobs (New Forests, 2012)

Chlorophyll fluorescence of stem cambial tissue reflects dormancy development in Juglans nigra seedlings - Barrett C. Wilson; Douglass F. Jacobs (New Forests, 2012)

Quantifying flooding effects on hardwood seedling survival and growth for bottomland restoration - John M. Kabrick; Daniel C. Dey; J. W. Van Sambeek; Mark V. Coggeshall; Douglass F. Jacobs (New Forests, 2012)

Mechanical site preparation for forest restoration - Magnus Löf; Daniel C. Dey; Rafael M. Navarro; Douglass F. Jacobs (New Forests, 2012)

Underplanting to sustain future stocking of oak (Quercus) in temperate deciduous forests - Daniel C. Dey; Emile S. Gardiner; Callie J. Schweitzer; John M. Kabrick; Douglass F. Jacobs (New Forests, 2012)

Leaf physiology and sugar concentrations of transplanted Quercus rubra seedlings in relation to nutrient and water availability - Joshua L. Sloan; Douglass F. Jacobs (New Forests, 2012)

Pruning methods to restore Castanea sativa stands attacked by Dryocosmus kuriphilus - Alberto Maltoni; Barbara Mariotti; Douglass F. Jacobs; Andrea Tani (New Forests, 2012)

Metropolitan area racial residential segregation, neighborhood racial composition, and breast cancer mortality - Emily F. Russell; Michael R. Kramer; Hannah L. F. Cooper; Sheryl Gabram-Mendola; Diana Senior-Crosby; Kimberly R. Jacob Arriola (Cancer Causes & Control, 2012)

Terpene production and growth of three Pacific Northwest conifers in response to simulated browse and nutrient availability - Owen T. Burney; Douglass F. Jacobs (Trees, 2012)

Evaporation from Heterogeneous and Sparse Canopies: On the Formulations Related to Multi-Source Representations - J. P. Lhomme; C. Montes; F. Jacob; L. Prévot (Boundary-Layer Meteorology, 2012)

Twenty year site preparation effects on sub-boreal lodgepole pine performance - Jacob O. Boateng; Jean L. Heineman; Lorne Bedford; Amanda F. Linnell Nemec; John McClarnon; R. Allan Powelson (New Forests, 2012)

An observational efficacy and safety analysis of the treatment of acute invasive aspergillosis using voriconazole - F. Jacobs; D. Selleslag; M. Aoun; A. Sonet; A. Gadisseur (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Brazilian psychiatric brain bank: a new contribution tool to network studies - K. C. de Oliveira; F. G. Nery; R. E. L. Ferreti; M. C. Lima; C. Cappi; A. Machado-Lima; L. Polichiso; L. L. Carreira; C. Ávila; A. T. D. L. Alho; H. P. Brentani; E. C. Miguel; et al. (Cell and Tissue Banking, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

A delineation of Nuclear Middle America biogeographical provinces based on river basin faunistic similarities - Wilfredo A. Matamoros; Brian R. Kreiser; Jacob F. Schaefer (Reviews in Fish Biology and Fisheries, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Sildenafil does not improve steady state cardiovascular hemodynamics, peak power, or 15-km time trial cycling performance at simulated moderate or high altitudes in men and women - Jochen Kressler; Mark Stoutenberg; Bernard A. Roos; Anne L. Friedlander; Arlette C. Perry; Joseph F. Signorile; Kevin A. Jacobs (European Journal of Applied Physiology, 2011)

Ecological and genetic assessment of spatial structure among replicate contact zones between two topminnow species - Jacob F. Schaefer; David D. Duvernell; Brian R. Kreiser (Evolutionary Ecology, 2011)

Imbalanced circulating matrix metalloproteinases in polycystic ovary syndrome - Valéria A. Gomes; Carolina S. Vieira; Anna L. Jacob-Ferreira; Vanessa A. Belo; Gustavo M. Soares; Janaína B. F. Fernandes; Rui A. Ferriani; Jose E. Tanus-Santos (Molecular and Cellular Biochemistry, 2011)

Nitrogen budgeting and quality of exponentially fertilized Quercus robur seedlings in Ireland - J. L. Schmal; D. F. Jacobs; C. O’Reilly (European Journal of Forest Research, 2011)

Trace element variations in olivine phenocrysts from Ugandan potassic rocks as clues to the chemical characteristics of parental magmas - Stephen F. Foley; Dorrit E. Jacob; Hugh St. C. O’Neill (Contributions to Mineralogy and Petrology, 2011)

Recent Advances in Wetland Delineation—Implications and impact of Regionalization - Jacob F. Berkowitz (Wetlands, 2011)

Proposed Hydrogeomorphic Classification for Wetlands of the Mid-Atlantic Region, USA - Robert P. Brooks; Mark M. Brinson; Kirk J. Havens; Carl S. Hershner; Richard D. Rheinhardt; Denice H. Wardrop; Dennis F. Whigham; Amy D. Jacobs; Jennifer M. Rubbo (Wetlands, 2011)

Improving balance function using vestibular stochastic resonance: optimizing stimulus characteristics - Ajitkumar P. Mulavara; Matthew J. Fiedler; Igor S. Kofman; Scott J. Wood; Jorge M. Serrador; Brian Peters; Helen S. Cohen; Millard F. Reschke; Jacob J. Bloomberg (Experimental Brain Research, 2011)

Characterization of toxins from the broad-banded water snake Helicops angulatus (Linnaeus, 1758): isolation of a cysteine-rich secretory protein, Helicopsin - Amalid Estrella; Elda E. Sánchez; Jacob A. Galán; W. Andy Tao; Belsy Guerrero; Luis F. Navarrete; Alexis Rodríguez-Acosta (Archives of Toxicology, 2011)

Half-sib seed source and nursery sowing density affect black walnut (Juglans nigra) growth after 5 years - K. E. Woeste; D. F. Jacobs; J. R. McKenna (New Forests, 2011)

Efficient mammalian germline transgenesis by cis-enhanced Sleeping Beauty transposition - Daniel F. Carlson; Aron M. Geurts; John R. Garbe; Chang-Won Park; Artur Rangel-Filho; Scott M. O’Grady; Howard J. Jacob; Clifford J. Steer; David A. Largaespada; Scott C. Fahrenkrug (Transgenic Research, 2011)

Editorial note - Douglass F. Jacobs (New Forests, 2011)

Atrophy in the parahippocampal gyrus as an early biomarker of Alzheimer’s disease - C. Echávarri; P. Aalten; H. B. M. Uylings; H. I. L. Jacobs; P. J. Visser; E. H. B. M. Gronenschild; F. R. J. Verhey; S. Burgmans (Brain Structure and Function, 2011)

Survival and competitiveness of Quercus rubra regeneration associated with planting stocktype and harvest opening intensity - Robert C. Morrissey; Douglass F. Jacobs; Anthony S. Davis; Ron A. Rathfon (New Forests, 2010)

Stable isotope variation in tooth enamel from Neogene hippopotamids: monitor of meso and global climate and rift dynamics on the Albertine Rift, Uganda - Thomas Christian Brachert; Gerhard B. Brügmann; Dieter F. Mertz; Ottmar Kullmer; Friedemann Schrenk; Dorrit E. Jacob; Immaculate Ssemmanda; Heinrich Taubald (International Journal of Earth Sciences, 2010)

Reproducibility of Standing Posture for X-Ray Radiography: A Feasibility Study of the BalancAid with Healthy Young Subjects - Dyah Ekashanti Octorina Dewi; Albert G. Veldhuizen; Johannes G. M. Burgerhof; I Ketut Eddy Purnama; Peter M. A. van Ooijen; Michael H. F. Wilkinson; Tati Latifah Erawati Rajab Mengko; Gijsbertus Jacob Verkerke (Annals of Biomedical Engineering, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Eighty years of meteorological observations at Wageningen, the Netherlands: precipitation and evapotranspiration - A. F. G. Jacobs; B. G. Heusinkveld; A. A. M. Holtslag (International Journal of Climatology, 2010)
Annual and seasonal characteristics of precipitation and evapotranspiration were analysed of an 80‐year data record (1928–2008) at Wageningen (the Netherlands). The precipitation series shows a mean annual rainfall of 765 ± 130 mm with a relatively high interannual variability [coefficient of variation (CV) = 17.0%]. Both the annual and seasonal rainfall trends show a small but statistically insignificant increase. Potential evapotranspiration was estimated by Makkink's formula, using observations of incoming solar radiation and air temperature as inputs. This provides a mean evapotranspiration of (525 ± 50) mm annum −1 with a relatively low interannual variability (CV = 9.5%). The annual and seasonal trends appear to be statistically significant, except for the summer season. In addition, since 1992, actual evapotranspiration is measured by the eddy‐covariance technique and these results were found to be highly correlated with the potential evapotranspiration ( E act ≈ 0.75 E pot ). A comparison is made with a class A evaporation pan operating between 1984 and 1989. Copyright © 2009 Royal Meteorological Society

Overstory species composition of naturally regenerated clearcuts in an ecological classification framework - Robert C. Morrissey; Douglass F. Jacobs; John R. Seifert; John A. Kershaw (Plant Ecology, 2010)

Fat frogs, mobile genes: unexpected phylogeographic patterns for the ornate chorus frog (Pseudacris ornata) - JACOB F. DEGNER; DIANA M. SILVA; TYLER D. HETHER; JUAN M. DAZA; ERIC A. HOFFMAN (Molecular Ecology, 2010)

A novel approach to locate Phytophthora infestans resistance genes on the potato genetic map - Mirjam M. J. Jacobs; Ben Vosman; Vivianne G. A. A. Vleeshouwers; Richard G. F. Visser; Betty Henken; Ronald G. van den Berg (Theoretical and Applied Genetics, 2010)

The earliest record of the genus Cola (Malvaceae sensu lato: Sterculioideae) from the Late Oligocene (28–27 Ma) of Ethiopia and leaf characteristics within the genus - Aaron David Pan; Bonnie F. Jacobs (Plant Systematics and Evolution, 2009)

Potato Transformation with Modified Nucleotide Sequences of the cry9Aa2 Gene Improves Resistance to Potato Tuber Moth - Jeanne M. E. Jacobs; Michael F. G. Takla; Lisa C. Docherty; Christina M. Frater; Ngaire P. Markwick; Sathiyamoorthy Meiyalaghan; Anthony J. Conner (Potato Research, 2009)

Sequencing the Potato Genome: Outline and First Results to Come from the Elucidation of the Sequence of the World’s Third Most Important Food Crop - Richard G. F. Visser; Christian W. B. Bachem; Jan M. de Boer; Glenn J. Bryan; Swarup K. Chakrabati; Sergio Feingold; Robert Gromadka; Roeland C. H. J. van Ham; Sanwen Huang; Jeanne M. E. Jacobs; Boris Kuznetsov; Paulo E. de Melo; et al. (American Journal of Potato Research, 2009)

Contractions but not AICAR increase FABPpm content in rat muscle sarcolemma - Jacob Jeppesen; Peter Albers; Joost J. Luiken; Jan F. C. Glatz; Bente Kiens (Molecular and Cellular Biochemistry, 2009)

Short-Term Physiological Responses of Black Walnut ( Juglans nigra L.) to Plantation Thinning - Martin-Michel Gauthier; Douglass F. Jacobs (Forest Science, 2009)
We studied physiological responses of mature black walnut (Juglans nigra L.) trees to determine the time necessary for photosynthetic adaptation to plantation thinning. Measurements were taken before treatment (July 25, 2007) and for the first 3 days after thinning (July 29, 30, and 31, 2007). Measurements did not continue in August because trees had developed leaf anthracnose and senescence was occurring, but measurements resumed on May 29, 2008 and July 29, 2008. Repeated measures of net photosynthetic rates (A) showed that thinned trees did not respond immediately to partial release, but nearly doubled in A compared with a 35% increase in control trees 1 year after thinning. Significant increases in light, leaf water status, relative humidity of the air, and nitrogen content per unit leaf area were also found in thinned trees 1 year after treatment. From these variables, light (r2 = 0.79) showed the strongest relationship with A. Results suggest that black walnut requires a full growing season before it responds to treatment when thinned late in the growing season. Thinning earlier, such as in June, may trigger a more rapid adaptation in A of thinned trees that was not detected in our study.

Field performance of Pinus halepensis planted in Mediterranean arid conditions: relative influence of seedling morphology and mineral nutrition - Juan A. Oliet; Rosa Planelles; Francisco Artero; Rosario Valverde; Douglass F. Jacobs; Maria L. Segura (New Forests, 2009)

Can Campylobacter coli induce Guillain-Barré syndrome? - A. van Belkum; B. Jacobs; E. van Beek; R. Louwen; W. van Rijs; L. Debruyne; M. Gilbert; J. Li; A. Jansz; F. Mégraud; H. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Performance and nutrient dynamics of holm oak (Quercus ilex L.) seedlings in relation to nursery nutrient loading and post-transplant fertility - Juan A. Oliet; María Tejada; K. Francis Salifu; Aleyda Collazos; Douglass F. Jacobs (European Journal of Forest Research, 2009)

Influence of agricultural practices on micrometerological spatial variations at local and regional scales - D. Courault; F. Jacob; V. Benoit; M. Weiss; O. Marloie; J. F. Hanocq; E. Fillol; A. Olioso; G. Dedieu; P. Gouaux; M. Gay; A. French (International Journal of Remote Sensing, 2009)

Root desiccation and drought stress responses of bareroot Quercus rubra seedlings treated with a hydrophilic polymer root dip - Kent G. Apostol; Douglass F. Jacobs; R. Kasten Dumroese (Plant and Soil, 2009)

Influence of sulfometuron methyl on conifer seedling root development - Owen T. Burney; Douglass F. Jacobs (New Forests, 2009)

Thermal remote sensing of the low‐intensity carbonatite volcanism of Oldoinyo Lengai, Tanzania - M. Kervyn; G. G. J. Ernst; A. J. L. Harris; F. Belton; E. Mbede; P. Jacobs (International Journal of Remote Sensing, 2008)

The effect of water turbidity on the near-surface water temperature of larval habitats of the malaria mosquito Anopheles gambiae - K. P. Paaijmans; W. Takken; A. K. Githeko; A. F. G. Jacobs (International Journal of Biometeorology, 2008)

A simplified model to predict diurnal water temperature dynamics in a shallow tropical water pool - Krijn P. Paaijmans; Bert G. Heusinkveld; Adrie F. G. Jacobs (International Journal of Biometeorology, 2008)

Nitrate reductase activity and nitrogen compounds in xylem exudate of Juglans nigra seedlings: relation to nitrogen source and supply - Michael A. Nicodemus; K. Francis Salifu; Douglass F. Jacobs (Trees, 2008)

An integrated modelling and remote sensing approach for hydrological study in arid and semi‐arid regions: the SUDMED Programme - A. Chehbouni; R. Escadafal; B. Duchemin; G. Boulet; V. Simonneaux; G. Dedieu; B. Mougenot; S. Khabba; H. Kharrou; P. Maisongrande; O. Merlin; A. Chaponnière; et al. (International Journal of Remote Sensing, 2008)

Synergistic Effect of Amlodipine and Atorvastatin in Reversing LDL-Induced Endothelial Dysfunction - R. Preston Mason; Ruslan Kubant; Gehan Heeba; Robert F. Jacob; Charles A. Day; Yehudi S. Medlin; Philipp Funovics; Tadeusz Malinski (Pharmaceutical Research, 2008)

Gold nanoparticles decorated with oligo(ethylene glycol) thiols: kinetics of colloid aggregation driven by depletion forces - Fajun Zhang; Donald G. Dressen; Maximilian W. A. Skoda; Robert M. J. Jacobs; Stefan Zorn; Richard A. Martin; Christopher M. Martin; Graham F. Clark; Frank Schreiber (European Biophysics Journal, 2008)

Threatened fishes of the world: Alosa alabamae (Jordan and Evermann, 1896) (Clupeidae) - Dwayne W. Meadows; Susan B. Adams; Jacob F. Schaefer (Environmental Biology of Fishes, 2008)

Diurnal temperature fluctuations in an artificial small shallow water body - Adrie F. G. Jacobs; Bert G. Heusinkveld; Aline Kraai; Krijn P. Paaijmans (International Journal of Biometeorology, 2008)

Mortality risks in patients with constitutional autosomal chromosome deletions in Britain: a cohort study - Anthony J. Swerdlow; Minouk J. Schoemaker; Craig D. Higgins; Alan F. Wright; Patricia A. Jacobs (Human Genetics, 2008)

Tests of reproductive isolation among species in the Fundulus notatus (Cyprinodontiformes: Fundulidae) species complex - Patrick A. Vigueira; Jacob F. Schaefer; David D. Duvernell; Brian R. Kreiser (Evolutionary Ecology, 2008)

Towards Closing the Surface Energy Budget of a Mid-latitude Grassland - Adrie F. G. Jacobs; Bert G. Heusinkveld; Albert A. M. Holtslag (Boundary-Layer Meteorology, 2008)

Atypical status of bovine spongiform encephalopathy in Poland: a molecular typing study - M. P. Polak; J. F. Zmudzinski; J. G. Jacobs; J. P. M. Langeveld (Archives of Virology, 2008)

Population genetics and conservation of the threatened southeastern beach mouse (Peromyscus polionotus niveiventris): subspecies and evolutionary units - Jacob F. Degner; I. Jack Stout; James D. Roth; Christopher L. Parkinson (Conservation Genetics, 2007)

Comparing functional assessments of wetlands to measurements of soil characteristics and nitrogen processing - Thomas E. Jordan; Mary Pittek Andrews; Ryan P. Szuch; Dennis F. Whigham; Donald E. Weller; Amy Deller Jacobs (Wetlands, 2007)

Combining HGM and EMAP procedures to assess wetlands at the watershed scale — status of flats and non-tidal riverine wetlands in the Nanticoke River watershed, Delaware and Maryland (USA) - Dennis F. Whigham; Amy Deller Jacobs; Donald E. Weller; Thomas E. Jordan; Mary E. Kentula; Susan F. Jensen; Donald L. Stevens (Wetlands, 2007)

Landscape indicators of wetland condition in the Nanticoke River watershed, Maryland and Delaware, USA - Donald E. Weller; Marcia N. Snyder; Dennis F. Whigham; Amy D. Jacobs; Thomas E. Jordan (Wetlands, 2007)

Mortality and cancer incidence in males with Y polysomy in Britain: a cohort study - Craig D. Higgins; Anthony J. Swerdlow; Minouk J. Schoemaker; Alan F. Wright; Patricia A. Jacobs (Human Genetics, 2007)

Providing a community-based cancer risk assessment service for a socially and ethnically diverse population - C. Jacobs; R. Rawson; C. Campion; C. Caulfield; J. Heath; C. Burton; F. Kavalier (Familial Cancer, 2007)

An intercomparison of regional climate simulations for Europe: assessing uncertainties in model projections - M. Déqué; D. P. Rowell; D. Lüthi; F. Giorgi; J. H. Christensen; B. Rockel; D. Jacob; E. Kjellström; M. de Castro; B. van den Hurk (Climatic Change, 2007)

Seasonal and interannual variability of carbon dioxide and water balances of a grassland - Adrie F. G. Jacobs; Bert G. Heusinkveld; Albert A. M. Holtslag (Climatic Change, 2007)

The influence of matrix attachment regions on transgene expression in Arabidopsis thaliana wild type and gene silencing mutants - Miguel F. C. De Bolle; Katleen M. J. Butaye; Inge J. W. M. Goderis; Piet F. J. Wouters; Anni Jacobs; Stijn L. Delauré; Ann Depicker; Bruno P. A. Cammue (Plant Molecular Biology, 2007)

Visual pigments of marine carnivores: pinnipeds, polar bear, and sea otter - David H. Levenson; Paul J. Ponganis; Michael A. Crognale; Jess F. Deegan; Andy Dizon; Gerald H. Jacobs (Journal of Comparative Physiology A, 2006)

Detecting Population Declines over Large Areas with Presence‐Absence, Time‐to‐Encounter, and Count Survey Methods - JACOB F. POLLOCK (Conservation Biology, 2006)
Ecologists often discount presence‐absence surveys as a poor way to gain insight into population dynamics, in part because these surveys are not amenable to many standard statistical tests. Still, presence‐absence surveys are sometimes the only feasible alternative for monitoring large areas when funds are limited, especially for sparse or difficult‐to‐detect species. I undertook a detailed simulation study to compare the power of presence‐absence, count, and time‐to‐encounter surveys to detect regional declines in a population. I used a modeling approach that simulates both population numbers and the monitoring process, accounting for observation and other measurement errors. In gauging the efficacy of presence‐absence surveys versus other approaches, I varied the number of survey sites, the spatial variation in encounter rate, the mean encounter rate, and the type of population loss. My results showed that presence‐absence data can be as or more powerful than count data in many cases. Quantitative guidelines for choosing between presence‐absence surveys and count surveys depend on the biological and logistical constraints governing a conservation monitoring situation. Generally, presence‐absence surveys work best when there is little variability in abundance among the survey sites, the organism is rare, and the species is difficult to detect so that the time spent getting to each survey site is less than or equal to the time spent surveying each site. Count surveys work best otherwise. I present a case study with count data on the Northern Flicker ( Colaptes auratus ) from the North American Breeding Bird Survey to illustrate how the method might be used with field‐survey data. The case study demonstrates that a count survey would be the most cost‐effective design but would entail reduction in the number of sites. If this site reduction is not desirable, a presence‐absence survey would be the most cost‐effective survey.

Quality Assessment of Temperate Zone Deciduous Hardwood Seedlings - Barrett C. Wilson; Douglass F. Jacobs (New Forests, 2006)

Ecomorphology and habitat utilization of Cottus species - James R. Kerfoot; Jacob F. Schaefer (Environmental Biology of Fishes, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Organic Matter Added to Bareroot Nursery Beds Influences Soil Properties and Morphology of Fraxinus pennsylvanica and Quercus rubra Seedlings - Anthony S. Davis; Douglass F. Jacobs; Kevyn E. Wightman; Zonda K. D. Birge (New Forests, 2006)

Hand preshaping in Parkinson’s disease: effects of visual feedback and medication state - Luis F. Schettino; Sergei V. Adamovich; Wayne Hening; Eugene Tunik; Jacob Sage; Howard Poizner (Experimental Brain Research, 2006)

Dopaminergic marker proteins in the substantia nigra of human immunodeficiency virus type 1–infected brains - Janelle M Silvers; Michael Y Aksenov; Marina V Aksenova; Jacob Beckley; Petra Olton; Charles F Mactutus; Rosemarie M Booze (Journal of NeuroVirology, 2006)

Effects of Urbanization on the Distribution and Abundance of Amphibians and Invasive Species in Southern California Streams - SETH P. D. RILEY; GARY T. BUSTEED; LEE B. KATS; THOMAS L. VANDERGON; LENA F. S. LEE; ROSI G. DAGIT; JACOB L. KERBY; ROBERT N. FISHER; RAYMOND M. SAUVAJOT (Conservation Biology, 2005)
Urbanization negatively affects natural ecosystems in many ways, and aquatic systems in particular. Urbanization is also cited as one of the potential contributors to recent dramatic declines in amphibian populations. From 2000 to 2002 we determined the distribution and abundance of native amphibians and exotic predators and characterized stream habitat and invertebrate communities in 35 streams in an urbanized landscape north of Los Angeles (U.S.A.). We measured watershed development as the percentage of area within each watershed occupied by urban land uses. Streams in more developed watersheds often had exotic crayfish (Procambarus clarkii) and fish, and had fewer native species such as California newts (Taricha torosa) and California treefrogs (Hyla cadaverina). These effects seemed particularly evident above 8% development, a result coincident with other urban stream studies that show negative impacts beginning at 10–15% urbanization. For Pacific treefrogs (H. regilla), the most widespread native amphibian, abundance was lower in the presence of exotic crayfish, although direct urbanization effects were not found. Benthic macroinvertebrate communities were also less diverse in urban streams, especially for sensitive species. Faunal community changes in urban streams may be related to changes in physical stream habitat, such as fewer pool and more run habitats and increased water depth and flow, leading to more permanent streams. Variation in stream permanence was particularly evident in 2002, a dry year when many natural streams were dry but urban streams were relatively unchanged. Urbanization has significantly altered stream habitat in this region and may enhance invasion by exotic species and negatively affect diversity and abundance of native amphibians.

Mortality and cancer incidence in women with extra X chromosomes: a cohort study in Britain - Anthony J. Swerdlow; Minouk J. Schoemaker; Craig D. Higgins; Alan F. Wright; Patricia A. Jacobs (Human Genetics, 2005)

Fertilizer-induced Changes in Rhizosphere Electrical Conductivity: Relation to Forest Tree Seedling Root System Growth and Function - Douglass F. Jacobs; Vic R. Timmer (New Forests, 2005)

Quantifying root system quality of nursery seedlings and relationship to outplanting performance - Anthony S. Davis; Douglass F. Jacobs (New Forests, 2005)

Simulation of Radon Transport through Building Materials: Influence of the Water Content on Radon Exhalation Rate - F. Fournier; J. E. Groetz; F. Jacob; J. M. Crolet; H. Lettner (Transport in Porous Media, 2005)

Bacillus cereus pneumonia in a patient with acute lymphoblastic leukemia - J. Frankard; R. Li; F. Taccone; M.J. Struelens; F. Jacobs; A. Kentos (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Establishment success of conservation tree plantations in relation to silvicultural practices in Indiana, USA - Douglass F. Jacobs; Amy L. Ross-Davis; Anthony S. Davis (New Forests, 2004)

Metapopulation ecology in the sea: from Levins' model to marine ecology and fisheries science - Jacob P Kritzer; Peter F Sale (Fish and Fisheries, 2004)
Marine and fisheries scientists are increasingly using metapopulation concepts to better understand and model their focal systems. Consequently, they are considering what defines a metapopulation. One perspective on this question emphasizes the importance of extinction probability in local populations. This view probably stems from the focus on extinction in Levins' original metapopulation model, but places unnecessary emphasis on extinction–recolonization dynamics. Metapopulation models with more complex structure than Levins' patch‐occupancy model and its variants allow a broader range of population phenomena to be examined, such as changes in population size, age structure and genetic structure. Analyses along these lines are critical in fisheries science, where presence–absence resolution is far too coarse to understand stock dynamics in a meaningful way. These more detailed investigations can, but need not, aim to assess extinction risk or deal with extinction‐prone local populations. Therefore, we emphasize the coupling of spatial scales as the defining feature of metapopulations. It is the degree of demographic connectivity that characterizes metapopulations, with the dynamics of local populations strongly dependent upon local demographic processes, but also influenced by a nontrivial element of external replenishment. Therefore, estimating rates of interpopulation exchange must be a research priority. We contrast metapopulations with other spatially structured populations that differ in the degree of local closure of their component populations. We conclude with consideration of the implications of metapopulation structure for spatially explicit management, particularly the design of marine protected area networks.

Haemophilus parainfluenzae : an Underdiagnosed Pathogen of Biliary Tract Infections? - J. Frankard; H. Rodriguez-Villalobos; M. J. Struelens; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Carbon dioxide and water vapour flux densities over a grassland area in the Netherlands - Adrie F. G. Jacobs; Bert G. Heusinkveld; Albert A. M. Holtslag (International Journal of Climatology, 2003)
Measurements of carbon dioxide and water vapour flux densities were carried out for a grassland area in the centre of the Netherlands during a 12 month continuous experiment using the eddy‐covariance technique. Lolium perenne and Poa trivialis mainly dominated the vegetation of the area. The leaf area index (LAI) of the grassland varied between 2.5 and 3.4, depending on the mowing scheme at the site. Fluxes are also calculated by using a canopy model in which the canopy resistance is related to the assimilation rate ( A – g s model). The calculated evapotranspiration fluxes agree within 7% of the measured fluxes ( R 2 = 0.93;SEE = 23 W m −2 ). The calculated net carbon dioxide fluxes agree within 12% of the measured fluxes ( R 2 = 0.79;SEE = 0.16 mg m −2 s −1 ). The net carbon dioxide fluxes consist of two opposite components: the uptake via assimilation and release via soil and plant respiration. It appears that nearly the whole year round the assimilation term dominates, which means an accumulation of carbon dioxide if no other exchange processes are present. For 2002 a net carbon uptake was found of 6.8 tonnes ha −1 . Copyright © 2003 Royal Meteorological Society

Influence of nursery soil amendments on water relations, root architectural development, and field performance of Douglas-fir transplants - Douglass F. Jacobs; Robin Rose; Diane L. Haase; Paul D. Morgan (New Forests, 2003)

Differential modulation of Bordetella pertussis virulence genes as evidenced by DNA microarray analysis - D. Hot; R. Antoine; G. Renauld-Mongénie; V. Caro; B. Hennuy; E. Levillain; L. Huot; G. Wittmann; D. Poncet; F. Jacob-Dubuisson; C. Guyard; F. Rimlinger; et al. (Molecular Genetics and Genomics, 2003)

Effects of Barriers and Thermal Refugia on Local Movement of the Threatened Leopard Darter, Percina pantherina - Jacob F. Schaefer; Edie Marsh-Matthews; Daniel E. Spooner; Keith B. Gido; William J. Matthews (Environmental Biology of Fishes, 2003)

The influence of temperature and climate change on the timing of pollen release in the Netherlands - Arnold J. H. van Vliet; Aart Overeem; Rudolf S. De Groot; Adrie F. G. Jacobs; Frits T. M. Spieksma (International Journal of Climatology, 2002)
In the last decade it has become clear that the timing of many phenological processes, like the start of flowering and leaf unfolding in spring, have changed. The increase in temperature is believed to be the main cause. The earlier start of flowering will have consequences for the start of the pollen season, and thus for the start of the hay fever season. Millions of people world‐wide will therefore experience the impact of climate change in their daily lives during spring and summer. In this paper we analyse the relation between climate parameters, especially temperature, and the start of the pollen season in the western part of the Netherlands based on daily pollen counts of the Leiden University Medical Centre and temperature measurements from 1969 till 2000 by the Royal Netherlands Meteorological Institute in De Bilt. The results indicate that there is a strong correlation between temperature and start of the pollen season. An advance of the start of the pollen season of 3 to 22 days has been observed. The potential future changes in the start of the pollen season under climate change scenarios are also discussed. Copyright © 2002 Royal Meteorological Society.

Behaviour of carbon dioxide and water vapour flux densities from a disturbed raised peat bog - Joost P. Nieveen; Adrie F. G. Jacobs (International Journal of Climatology, 2002)
Measurements of carbon dioxide and water vapour flux densities were carried out for a disturbed raised peat bog in the north of the Netherlands during an 18 month continuous experiment. Tussock grass (sp. Molinea caerulae ) mainly dominated the vegetation of the bog area. The maximum leaf area index (LAI) of the vegetation reached a numerical value of about 1.7 in mid‐August. When the LAI is large enough (LAI > 0.2), a mean net uptake of carbon dioxide is observed with a clear daily pattern. The total evapotranspiration consists of a soil, an open water, and a plant transpiration part. When the LAI is large enough (LAI > 0.2), plant transpiration dominates the total evapotranspiration. The mean daily transpiration pattern, however, is not similar to the carbon dioxide uptake pattern. During the summer months, the daytime carbon dioxide uptake shows a single early morning maximum value followed by a decline in uptake during the rest of the day. The evapotranspiration, however, follows more or less the incoming short‐wave radiation pattern. Effects of the vapour pressure deficit are suggested as a possible cause of this discrepancy. Copyright © 2002 Royal Meteorological Society.

High-resolution mapping of the bolting gene B of sugar beet - A. El-Mezawy; F. Dreyer; G. Jacobs; C. Jung (Theoretical and Applied Genetics, 2002)

Evapotranspiration from a wet prairie wetland under drought conditions: Paynes prairie preserve, Florida, USA - Jennifer M. Jacobs; Shannon L. Mergelsberg; Andres F. Lopera; David A. Myers (Wetlands, 2002)

Genetic diversity, mating system, and conservation of a Mexican subalpine relict, Picea mexicana Martínez - F. Thomas Ledig; Paul D. Hodgskiss; Virginia Jacob-Cervantes (Conservation Genetics, 2002)

A normal ocular motor system model that simulates the dual-mode fast phases of latent/manifest latent nystagmus - L. F. Dell'Osso; J. B. Jacobs (Biological Cybernetics, 2001)

Ceftazidime- and Imipenem-Induced Endotoxin Release During Treatment of Gram-Negative Infections - B. Byl; P. Clevenbergh; A. Kentos; F. Jacobs; A. Marchant; J. Vincent; J. Thys (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)

Elevated Serum Homocysteine levels and Increased risk of Invasive Cervical Cancer in US Women - Stephanie J. Weinstein; Regina G. Ziegler; Jacob Selhub; Thomas R. Fears; Howard D. Strickler; Louise A. Brinton; Richard F. Hamman; Robert S. Levine; Katherine Mallin; Paul D. Stolley (Cancer Causes & Control, 2001)

Dew measurements along a longitudinal sand dune transect, Negev Desert, Israel - A. F. G. Jacobs; B. G. Heusinkveld; S. M. Berkowicz (International Journal of Biometeorology, 2000)

Gulf of Mexico Monitoring System - John Blaha; George Born; Norman Guinasso; James Herring; Gregg Jacobs; F. Kelley; Robert Leban; Robert Martin; George Mellor; Peter Niiler; Michael Parke; Richard Patchen; et al. (Oceanography, 2000)

Physiological Performance and Stream Microhabitat use by the Centrarchids Lepomis megalotis and Lepomis macrochirus - Jacob F. Schaefer; William I. Lutterschmidt; Loren G. Hill (Environmental Biology of Fishes, 1999)

Diurnal and seasonal variation of carbon dioxide exchange from a former true raised bog - JOOST P. NIEVEEN; COR. M. J. JACOBS; ADRIE F. G. JACOBS (Global Change Biology, 1998)
Carbon dioxide exchange was measured, using the eddy covariance technique, during a one and a half year period in 1994 and 1995. The measurements took place over a former true raised bog, characterized by a shallow peat layer and a vegetation dominated by Molinia caerulea . The growing season extended from May until late October, with a maximum LAI in August of 1.7. The carbon balance shows a net release of 97 g C m –2 y –1 (265 kg C ha –1 y –1 ) from the peat bog ecosystem to the atmosphere. During June, July and August there is net consumption of CO 2 , while during the rest of the year there is net production of CO 2 . The average daytime assimilation rates ranged between – 0.2 and – 0.5 mg CO 2 m –2 s –1 (– 45 and –11.3 μmol CO 2 m –2 s –1 ), in a period where the LAI ranged between 1 and 1.7. A high vapour pressure deficit (> 15 hPa) corresponding with high temperatures was found to reduce the assimilation rate by on average 50%. Apart from these factors, LAI and the soil temperature codetermine the net exchange of CO 2 . The total nocturnal respiration during the growing season lies within the same order as the average daytime net assimilation rate. Temperature was found to be the main factor controlling soil respiration, with a Q 10 of 4.8.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Clean catalytic technology for liquid phase hydrocarbon oxidation - G. Langhendries; D. E. De Vos; B. F. Sels; I. Vankelecom; P. A. Jacobs; G. V. Baron (Clean Technologies and Environmental Policy, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Acquisition of nicotine self-administration in rats: the effects of dose, feeding schedule, and drug contingency - Eric C. Donny; A. R. Caggiula; Michelle M. Mielke; Kimberly S. Jacobs; Christine Rose; Alan F. Sved (Psychopharmacology, 1998)

Temperature Behavior of a Natural Shallow Water Body during a Summer Period - A. F. G. Jacobs; B. G. Heusinkveld; J. P. Nieveen (Theoretical and Applied Climatology, 1998)

UV irradiation as a tool for obtaining asymmetric somatic hybrids between Nicotiana plumbaginifolia and Lycopersicon esculentum - M. Vlahova; S. Hinnisdaels; F. Frulleux; M. Claeys; A. Atanassov; M. Jacobs (Theoretical and Applied Genetics, 1997)

Urinary and faecal excretion of chrysene and chrysene metabolites by rats after oral, intraperitoneal, intratracheal or intrapulmonary application - G. Grimmer; H. Brune; G. Dettbarn; U. Heinrich; J. Jacob; E. Mohtashamipur; K. Norpoth; F. Pott; R. Wenzel-Hartung (Archives of Toxicology, 1988)

Transducer system for the noninvasive recording of arterial pressure contours - S. G. Karr; T. Karwoski; J. E. Jacobs; L. F. Mockros (Annals of Biomedical Engineering, 1985)

Comparison of primary structures of fimbrial subunits of pathogenicEscherichia coli strains - E. Roosendaal; T. Jacobs; F. K. de Graaf (Antonie van Leeuwenhoek, 1985)